Electrophotographic developer set including toner and powder adhesive and method for making adhesive
The electrophotographic developer set with a toner and powder adhesive having specific viscoelastic properties addresses the challenge of achieving both strong adhesion and high-temperature offset resistance, enabling efficient printing and bag formation.
Patent Information
- Application Number
- JP2020130346
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-07-31
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2040-07-31
AI Technical Summary
Existing electrophotographic methods face challenges in achieving both sufficient adhesive strength and high-temperature offset resistance when using toner and powder adhesive, particularly in creating paper bags with printed information, as they often result in inadequate adhesion or transfer of the image to the fixing device.
An electrophotographic developer set comprising a toner and a powder adhesive with specific viscoelastic properties, including a crystalline polyester resin content of 21% by mass or more and a melting point of 55°C to 100°C, and a storage modulus ratio Gt'(100)/Gb'(100) of 1.2 or more, ensures both strong adhesion and resistance to high-temperature offset.
The developer set provides excellent adhesive strength and high-temperature offset resistance, allowing for effective printing on plain paper and conversion into paper bags without image transfer to the fixing device.
Smart Images

Figure 0007618408000011 
Figure 0007618408000012 
Figure 0007618408000013
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrophotographic developer set that uses an electrophotographic method to develop an electrostatic latent image on a recording material to form a toner image and an adhesive part made of a powder adhesive that functions as an adhesive, the developer set including a toner and a powder adhesive. The present disclosure also relates to a method for producing an adhesive product using the electrophotographic developer set. [Background technology]
[0002] Conventionally, when using a printer or copier to create paper bags with different information printed on them for each individual, a pre-made paper bag would be set in the printer or copier and printed on. Therefore, when printing on paper bags and on plain paper at the same time, there was a problem that the paper used in the printer had to be changed from the paper bag to plain paper every time the printing target was changed, or the printing target was printed on the wrong target. In response to the above problems, a method has been proposed in which, in addition to forming an image using color toners by electrophotography, a bonding section is formed using a powder adhesive that does not contain pigments, and then the paper is bonded. A method has also been proposed in which, by using this method, printing is performed on plain paper and the plain paper is simultaneously processed into a paper bag. A toner set of color toner and powder adhesive for use in this method has also been proposed. Furthermore, a set of a color toner and a transparent toner has been proposed for the purpose of imparting a three-dimensional effect, a glossy effect, and granularity to applications other than adhesives. Patent Document 1 proposes an image forming method in which an image and an adhesive portion are formed using an adhesive toner having a lower limit of an appropriate fixing temperature than a toner for image formation. Patent Document 2 proposes a toner set in which a layer of transparent toner is formed on an image formed with color toners, to give the image a visually three-dimensional appearance. Patent Document 3 proposes a toner set that uses a transparent toner to control the glossiness of the entire image. Patent Document 4 proposes a toner set that uses a transparent toner to control the graininess of a solid image. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2006-171607 A [Patent Document 2] JP 2013-130794 A [Patent Document 3] JP 2014-139618 A [Patent Document 4] JP 2014-153661 A Summary of the Invention [Problem to be solved by the invention]
[0004] The method described in Patent Document 1 discloses that by using an adhesive toner whose minimum optimum fixing temperature is lower than that of the image-forming toner, the adhesive toner can be melted at a temperature at which the image-forming toner does not melt. However, when this method is used to create a paper bag by forming an image area on paper using toner, forming an adhesive area using powder adhesive on the back side of the image area, stacking the paper with the adhesive area on the inside, and melting the adhesive area, it has been found that sufficient adhesive strength may not be obtained. Furthermore, when the adhesive portion is heated to a high temperature and melted in order to obtain a strong adhesive force, the image portion may melt and part of the image portion may transfer to the fixing unit (high-temperature offset property), and it has been found that it is difficult to achieve both strong adhesive force and high-temperature offset resistance. On the other hand, the toner sets described in Patent Documents 2 to 4 aim to provide three-dimensional effect, glossiness, and granularity using transparent toner, respectively. Therefore, when using transparent toner as a powder adhesive, there is a problem that it is difficult to achieve both sufficient adhesive strength and high-temperature offset resistance of color toner. The present disclosure provides an electrophotographic developer set including a toner and a powder adhesive, which has excellent high-temperature offset resistance and sufficient adhesive strength, and a method for producing an adhesive product using the electrophotographic developer set. [Means for solving the problem]
[0005] 1. An electrophotographic developer set including a toner and a powder adhesive, The powder adhesive contains a crystalline polyester resin and a thermoplastic resin other than the crystalline polyester resin, The content of the crystalline polyester resin in the powder adhesive is 21% by mass or more, The melting point of the crystalline polyester resin is 55° C. or more and 100° C. or less, In viscoelastic measurements, The storage modulus of the toner at 100° C. is Gt'(100), When the storage modulus of the powder adhesive at 100°C is Gb'(100), Gb'(100) is 1.0×10 5 Pa or less, An electrophotographic developer set in which Gt'(100) / Gb'(100) is 1.2 or more. Effect of the Invention
[0006] According to the present disclosure, it is possible to provide an electrophotographic developer set including a toner and a powder adhesive, which has excellent high-temperature offset resistance and sufficient adhesive strength, and a method for producing an adhesive product using the electrophotographic developer set. [Brief description of the drawings]
[0007] [Figure 1] Schematic diagram of an image forming apparatus [Diagram 2] FIG. 2 is a diagram for explaining attachment of an adhesive unit to a main body of an image forming apparatus; [Diagram 3] FIG. 1 is a diagram showing a sheet transport path in an image forming apparatus; [Figure 4] A diagram to explain the folding process [Diagram 5] FIG. 1 is a perspective view showing an external appearance of an image forming apparatus; [Figure 6] FIG. 1 is a diagram illustrating an example of a product output by an image forming apparatus. [Figure 7]Schematic diagram of a process cartridge [Figure 8] Schematic diagram of evaluation sample [Figure 9] Schematic diagram of evaluation sample [Figure 10] Schematic diagram of evaluation sample [Figure 11] Schematic diagram of adhesive strength evaluation DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] In the present disclosure, the expressions "XX or more and YY or less" and "XX to YY" representing a numerical range mean a numerical range including the endpoints, that is, the lower limit and the upper limit, unless otherwise specified. When numerical ranges are stated in stages, the upper and lower limits of each numerical range can be combined in any way. The methods for measuring the various physical properties will be described below.
[0009] First, an example of a method for producing a paper bag by an electrophotographic method using an electrophotographic developer set containing the above toner and powder adhesive will be described below. First, an image portion is developed on a sheet of paper using toner by electrophotography (image portion developing process). Next, the image portion is fixed onto the sheet of paper by heating (image portion fixing process). Next, an adhesive portion is developed on the back side of the sheet of paper on which the image portion is formed using a powder adhesive (adhesive portion developing process). ) Next, the adhesive is fixed onto the paper by heating (adhesive fixing process). After that, the paper is stacked with the adhesive sandwiched between them and heated again to melt the adhesive (adhesive process), resulting in a paper bag (finished product).
[0010] To prevent the adhesive from peeling off even when an object is placed in the finished product, it is important to increase the adhesive strength between the powder adhesive and the paper, but at the same time, it is necessary to prevent high temperature offset of the image area. Here, the inventors considered that in order to achieve sufficient adhesive strength at the adhesive part in the adhesion process and at the same time prevent high-temperature offset of the image part, it is important to control the melt viscosity of the powder adhesive and the toner, and conducted extensive research.
[0011] The present disclosure provides an electrophotographic developer set including a toner and a powder adhesive, The powder adhesive contains a crystalline polyester resin and a thermoplastic resin other than the crystalline polyester resin, The content of the crystalline polyester resin in the powder adhesive is 21% by mass or more, The melting point of the crystalline polyester resin is 55° C. or more and 100° C. or less, In viscoelastic measurements, The storage modulus of the toner at 100° C. is Gt'(100), When the storage modulus of the powder adhesive at 100°C is Gb'(100), Gb'(100) is 1.0×10 5 Pa or less, The electrophotographic developer set has a Gt'(100) / Gb'(100) ratio of 1.2 or more.
[0012] By controlling the physical properties of the developer set within the above ranges, it becomes possible to achieve both sufficient adhesive strength and offset resistance. The present inventors believe that the reason for this is as follows. During the bonding process, the adhesive part cannot receive heat directly from the fuser because there is paper between the adhesive part and the fuser, so the powder adhesive needs to be designed with a viscosity that allows it to melt sufficiently even if the heat from the fuser is partially blocked by the paper. Furthermore, in order for the powder adhesive to exert sufficient adhesive strength, it is important not only to form the adhesive part of the powder adhesive as an image on the paper, but also to design it so that it penetrates into the paper fibers when melted. When the molten powder adhesive penetrates into the paper fibers and hardens, it exerts a so-called anchor effect, which increases the adhesive strength. In other words, in order to obtain adhesive strength, it is important for the adhesive to quickly become low viscosity when melted and to penetrate into the paper fibers.
[0013] The powder adhesive contains a crystalline polyester resin and a thermoplastic resin other than the crystalline polyester resin (hereinafter, simply referred to as "thermoplastic resin"). The crystalline polyester resin has a sharp melting property and can melt quickly even when passing through a fixing device. In addition, the molten crystalline polyester resin mixes with the thermoplastic resin and can reduce the melt viscosity of the thermoplastic resin. Furthermore, because crystalline polyester resin has a polar ester bond in its molecular structure, it has excellent compatibility with paper, so the molten powder adhesive easily penetrates into the paper fibers due to capillary action.
[0014] The content of the crystalline polyester resin in the powder adhesive is 21% by mass or more. The content is preferably 25% by mass or more and 40% by mass or less. By making the content 21% by mass or more, the powder adhesive can be melted in a short time at the time of fixing and can have a low viscosity. By making the viscosity low, it becomes easier for the adhesive to penetrate into the paper fibers, and the adhesive strength can be increased.
[0015] The melting point of the crystalline polyester resin contained in the powder adhesive is 55° C. or more and 100° C. or less. The melting point is preferably 55° C. or more and 90° C. or less. By setting the viscosity within the above range, the viscosity can be reduced even with a small amount of heat, making it easier for the adhesive to penetrate into the paper fibers and increasing the adhesive strength.
[0016] In the viscoelasticity measurement of a powder adhesive, when the storage modulus of the powder adhesive at 100°C is Gb'(100), Gb'(100) is 1.0×10 5 Pa or less. Gb'(100) is preferably 1.0×10 4 The lower limit is not particularly limited, but is preferably 1.0×10 Pa or more, and more preferably 1.0×10 2 Pa or more. The powder adhesive needs to be designed with a viscosity that allows it to melt even when the heat from the fixing unit is partially blocked by paper, and it was found that not only the viscosity when molten but also the storage modulus at 100°C is important for obtaining adhesive strength. The storage modulus is an index of how easily something deforms, and the smaller the value, the more difficult it is to return to its original shape when deformed. Gb'(100) is 1.0×10 5 If the pressure is less than Pa, the powder adhesive melted by heat will deform when subjected to pressure and will be able to penetrate into the paper fibers, providing sufficient adhesive strength.
[0017] While the powder adhesive achieves sufficient adhesive strength, it is necessary to suppress the occurrence of high-temperature offset in the toner image formed on the front side of the paper bag. There is no shielding between the toner image and the fixing unit, so the toner image is directly exposed to heat. Therefore, if the toner is deformed too much due to heat and pressure, part of the toner will transfer to the fixing unit, causing high-temperature offset. In measuring the viscoelasticity of toner, when the storage modulus of the toner at 100°C is Gt'(100), it is important to set the Gt'(100) of the toner within a range in which the toner is not too deformed by the heat and pressure of the fixing unit, relative to Gb'(100), which is the index of deformation of the powder adhesive due to the heat and pressure of the fixing unit.
[0018] As a result of intensive research by the present inventors, it was found that if Gt'(100) / Gb'(100) is 1.2 or more, sufficient adhesive strength of the powder adhesive and high-temperature offset resistance of the toner can be achieved at the same time. Gt'(100) / Gb'(100) is preferably 2.0 to 30.0, and more preferably 5.0 to 25.0. Gb'(100) and Gt'(100) can be controlled by the types and amount ratios of the thermoplastic resin and crystalline polyester contained in the powder adhesive and toner. Gt'(100) is preferably 5.0×10 3 Pa~1.0×10 5 Pa, more preferably 2.0×10 4 Pa ~ 6.0 × 10 4 It is Pa.
[0019] In order to further improve the adhesive strength of the powder adhesive and the high-temperature offset resistance of the toner, the storage modulus Gb' of the powder adhesive and the storage modulus Gt' of the toner should be 1.0×10 4 It is preferable to control the temperature relationship at which the pressure becomes 1 Pa. The storage modulus Gb' of the powder adhesive is 1.0×10 4 If the toner has a storage modulus Gt' of 1.0 x 10 Pa, it will deform due to the heat and pressure of the fixing unit and penetrate into the paper fibers, providing adhesive strength. 4 When the storage modulus of the powder adhesive and toner is 1.0×10 Pa, high temperature offset is unlikely to occur. 4 The temperature at this temperature of 1 Pa is a guide for further improving the adhesive strength of the powder adhesive and the high-temperature offset resistance of the toner.
[0020] Because the toner is directly heated by the fixing unit, the storage modulus of the toner, Gt', is 1.0×10 at a higher temperature than the powder adhesive. 4 In viscoelasticity measurements, the storage modulus Gb' of the powder adhesive is ideally 1.0×10 Pa. 4 The temperature at which the toner storage elastic modulus Gt' is 1.0×10 4 When the temperature at which the viscosity becomes 1 Pa is defined as Tt, Tt-Tb is preferably 10° C. or higher, and more preferably 15° C. or higher. By setting Tt-Tb at 10° C. or more, it becomes easier to achieve both sufficient adhesive strength of the powder adhesive and high-temperature offset resistance of the toner. There is no particular upper limit, but Tt-Tb is preferably 35° C. or less, and more preferably 30° C. or less. Tb and Tt can be controlled by the types and amount ratios of the thermoplastic resin and the crystalline polyester resin contained in the powder adhesive and the toner.
[0021] In the viscoelasticity measurement of the powder adhesive, the maximum ratio (tan δ) of the loss modulus G″ to the storage modulus G′ of the powder adhesive in the temperature range of 55° C. to 100° C. is preferably less than 3.0, and more preferably 0.7 to 2.0. Tan δ is an index that represents the viscosity of a powder adhesive when molten; the smaller the tan δ, the closer the adhesive is to an elastic body, and the larger the tan δ, the closer the adhesive is to a viscous body.
[0022] When the maximum value of tan δ is less than 3.0, the molten powder adhesive behaves like an elastic body. Therefore, even if misalignment occurs between the papers as they pass through the fixing unit, the molten powder adhesive returns to its original shape, eliminating the misalignment between the papers and suppressing the occurrence of wrinkles. The tan δ can be controlled by the types and amount ratios of the thermoplastic resin, the crystalline polyester resin and the wax contained in the powder adhesive.
[0023] The powder adhesive contains a thermoplastic resin other than the crystalline polyester resin. The thermoplastic resin contained in the powder adhesive is not particularly limited, and examples thereof include known thermoplastic resins such as polyester resin, vinyl resin, acrylic resin, styrene-acrylic resin, polyethylene, polypropylene, polyolefin, ethylene-vinyl acetate copolymer resin, and ethylene-acrylic acid copolymer resin. The toner may also contain a thermoplastic resin as described above. The toner and the powder adhesive may contain a plurality of these resins. The thermoplastic resins contained in the toner and the powder adhesive may be the same or different.
[0024] The thermoplastic resin other than the crystalline polyester resin contained in the powder adhesive preferably contains an amorphous resin. The thermoplastic resin other than the crystalline polyester resin preferably contains an amorphous polyester resin as a main component. The main component indicates that the content is 50 mass% or more. The toner preferably contains an amorphous resin as the thermoplastic resin, and more preferably contains an amorphous polyester resin. The content of the amorphous polyester resin in the thermoplastic resin is preferably 50% by mass to 100% by mass, more preferably 80% by mass to 100% by mass, and further preferably 90% by mass to 100% by mass.
[0025] Both amorphous polyester resin and crystalline polyester resin have a polar ester bond in their molecular structure, so they have a high affinity and blend easily even when melted. Therefore, the crystalline polyester resin does not easily separate from the amorphous polyester resin when the powder adhesive is melted. This prevents the separated crystalline polyester resin from penetrating the paper and seeping out to the opposite side of the adhesive surface of the paper. The content of the thermoplastic resin other than the crystalline polyester resin in the powder adhesive is preferably 40% by mass to 80% by mass, and more preferably 50% by mass to 65% by mass.
[0026] As the amorphous polyester resin, a known polyester resin can be used. Specific examples include condensation polymers of dibasic acids and their derivatives (carboxylic acid halides, esters, acid anhydrides) and dihydric alcohols. If necessary, trivalent or higher polybasic acids and their derivatives (carboxylic acid halides, esters, acid anhydrides), monobasic acids, trivalent or higher alcohols, and monohydric alcohols may also be used.
[0027] Examples of dibasic acids include maleic acid, fumaric acid, itaconic acid, oxalic acid, malonic acid, aliphatic dibasic acids such as succinic acid, dodecylsuccinic acid, dodecenylsuccinic acid, adipic acid, azelaic acid, sebacic acid, and decane-1,10-dicarboxylic acid; aromatic dibasic acids such as phthalic acid, tetrahydrophthalic acid, hexahydrophthalic acid, tetrabromophthalic acid, tetrachlorophthalic acid, HET acid, himic acid, isophthalic acid, terephthalic acid, and 2,6-naphthalenedicarboxylic acid; and the like. Furthermore, examples of derivatives of dibasic acids include carboxylic acid halides, esters and acid anhydrides of the above aliphatic dibasic acids and aromatic dibasic acids.
[0028] On the other hand, examples of dihydric alcohols include acyclic aliphatic diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, diethylene glycol, dipropylene glycol, triethylene glycol, and neopentyl glycol; bisphenols such as bisphenol A and bisphenol F; alkylene oxide adducts of bisphenol A such as an ethylene oxide adduct of bisphenol A and a propylene oxide adduct of bisphenol A; and aralkylene glycols such as xylylenediglycol.
[0029] Examples of trivalent or higher polybasic acids and anhydrides thereof include trimellitic acid, trimellitic anhydride, pyromellitic acid, and pyromellitic anhydride.
[0030] Examples of polymerizable monomers capable of forming the styrene-acrylic resin include styrene-based monomers such as styrene, α-methylstyrene, and divinylbenzene; unsaturated carboxylic acid esters such as methyl acrylate, butyl acrylate, methyl methacrylate, 2-hydroxyethyl methacrylate, t-butyl methacrylate, and 2-ethylhexyl methacrylate; unsaturated carboxylic acids such as acrylic acid and methacrylic acid; unsaturated dicarboxylic acids such as maleic acid; unsaturated dicarboxylic anhydrides such as maleic anhydride; nitrile-based vinyl monomers such as acrylonitrile; halogen-containing vinyl monomers such as vinyl chloride; and nitro-based vinyl monomers such as nitrostyrene. These may be used alone or in combination.
[0031] The number average molecular weight Mn of the thermoplastic resin is preferably 5,000 to 50,000, and more preferably 10,000 to 40,000. The weight average molecular weight Mw of the thermoplastic resin is preferably 20,000 to 200,000, and more preferably 50,000 to 150,000. The glass transition temperature Tg of the thermoplastic resin is preferably 40°C to 90°C, and more preferably 50°C to 65°C.
[0032] The crystalline polyester resin contained in the powder adhesive may be any known crystalline polyester resin. The crystalline resin is a resin that shows a clear melting point when measured using a differential scanning calorimeter (DSC). The crystalline polyester resin is preferably a condensation polymer of a monomer containing an aliphatic diol and / or an aliphatic dicarboxylic acid. The crystalline polyester resin preferably contains a structure derived from an aliphatic diol having 2 to 12 (preferably 2 to 10) carbon atoms and / or a structure derived from an aliphatic dicarboxylic acid having 2 to 12 (preferably 2 to 10) carbon atoms. The crystalline polyester resin is more preferably a condensation polymer of an aliphatic diol having 2 to 12 (preferably 2 to 10) carbon atoms and an aliphatic dicarboxylic acid having 2 to 12 (preferably 2 to 10) carbon atoms.
[0033] Crystalline polyester resins having such a structure have molecules regularly arranged and have excellent sharp melting properties, so they can be melted quickly during fixing. It also has the effect of lowering the viscosity of plastic resin. Some thermoplastic resins have hydrogen bonds between the molecules that make up the resin, so the viscosity of the thermoplastic resin itself cannot be sufficiently reduced even when it is melted. The crystalline polyester resin having the above structure easily penetrates between the molecules of the thermoplastic resin when melted, and acts to weaken the hydrogen bonds in the thermoplastic resin, which is effective in reducing the viscosity of the powder adhesive. Furthermore, the polarity of the ester groups in the crystalline polyester resin works favorably in terms of compatibility with paper. These properties allow the molten powder adhesive to easily penetrate the paper fibers by capillary action, increasing adhesive strength.
[0034] Examples of the aliphatic diol having 2 to 12 carbon atoms include the following compounds. 1,2-ethanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol. In addition, an aliphatic diol having a double bond can also be used. Examples of the aliphatic diol having a double bond include the following compounds. 2-butene-1,4-diol, 3-hexene-1,6-diol and 4-octene-1,8-diol.
[0035] Examples of the aliphatic dicarboxylic acid having 2 to 12 carbon atoms include the following compounds. Oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,11-undecanedicarboxylic acid, 1,12-dodecanedicarboxylic acid. Lower alkyl esters and acid anhydrides of these aliphatic dicarboxylic acids can also be used. These can be used alone or in combination of two or more.
[0036] The method for producing the crystalline polyester resin is not particularly limited, and the crystalline polyester resin can be produced by a general polyester polymerization method in which a dicarboxylic acid component and a diol component are reacted. For example, the crystalline polyester resin can be produced by a direct polycondensation method or an ester exchange method, which are selected depending on the type of monomer. The crystalline polyester resin contained in the powder adhesive preferably has a number average molecular weight Mn of 6200 to 20000. When the molecular weight Mn is within this range, the viscosity of the molten crystalline polyester resin when mixed with the thermoplastic resin can be appropriately controlled. Therefore, when the powder adhesive passes through the fixing unit, deviations in the transport of the paper and the occurrence of wrinkles in the paper can be prevented.
[0037] The toner preferably contains a crystalline polyester resin. The crystalline polyester resin used in the toner may be selected from those described in the crystalline polyester resins used in the powder adhesive. In order to achieve both the adhesive strength of the powder adhesive and the high-temperature offset resistance of the toner, it is preferable that the content of the crystalline polyester resin in the toner is less than the content of the crystalline polyester resin in the powder adhesive. The content of the crystalline polyester resin in the toner is preferably from 2% by mass to 25% by mass, and more preferably from 5% by mass to 20% by mass.
[0038] The toners and powder adhesives may contain colorants, including black colorants, yellow colorants, magenta colorants, and cyan colorants. Examples of black colorants include carbon black. Yellow colorants include monoazo compounds, disazo compounds, condensed azo compounds, and isoazo compounds. Yellow pigments such as indolinone compounds, isoindoline compounds, benzimidazolone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds are exemplified. Specific examples include CI Pigment Yellow 74, 93, 95, 109, 111, 128, 155, 174, 180, and 185.
[0039] Magenta colorants include magenta pigments such as monoazo compounds, condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds. Specific examples include CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 150, 166, 169, 177, 184, 185, 202, 206, 220, 221, 238, 254, and 269, and CI Pigment Violet Red 19.
[0040] Examples of cyan colorants include cyan pigments such as copper phthalocyanine compounds and their derivatives, anthraquinone compounds, basic dye lake compounds, etc. Specific examples include CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, and 66. In addition to the pigment, various dyes conventionally known as colorants can also be used. The content of the colorant in the toner is preferably from 1.0% by mass to 20.0% by mass. The powder adhesive preferably contains a colorant. The content of the colorant in the powder adhesive is preferably more than 0.00% by mass and not more than 1.00% by mass, more preferably 0.01% by mass or more and 0.50% by mass or less, and even more preferably 0.02% by mass or more and 0.10% by mass or less. By containing a colorant in the powder adhesive, curling of the product obtained by bonding two pieces of paper together during fixing can be suppressed.
[0041] The curl occurs when the adhesive part is deformed when the product cools after passing through the fixing device. The crystalline polyester resin in the powder adhesive is preferably present in a finely dispersed state within the powder adhesive particles. Even when the powder adhesive melts, the crystalline polyester resin tends to maintain a suitable finely dispersed state with the colorant particles as nuclei. Therefore, when fine colorant particles are present in the powder adhesive particles, the crystalline polyester resin tends to remain finely dispersed when melted, making it less likely to shrink when cured and helping to prevent curling.
[0042] The powder adhesive preferably contains a polyvalent metal compound, which is preferably at least one selected from the group consisting of an aluminum compound, an iron compound, and a magnesium compound. Examples of polyvalent metal compounds used in powder adhesives include inorganic metal salts, divalent or higher metal complexes, etc. Examples of inorganic metal salts include metal salts such as sodium chloride, calcium chloride, calcium nitrate, barium chloride, magnesium chloride, magnesium sulfate, zinc chloride, aluminum chloride, aluminum sulfate, and iron chloride, as well as inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide. The polyvalent metal compound is more preferably at least one selected from the group consisting of aluminum chloride, iron chloride, magnesium chloride, and sodium chloride.
[0043] Polyvalent metal compounds have ionic bonds, and the metal elements are biased toward positive charging. On the other hand, in crystalline polyester resins, the carbonyl groups in the ester groups are biased toward negative charging. As a result, the metal element portion of the polyvalent metal compound and the carbonyl group of the crystalline polyester resin are attracted to each other. It has become a situation like this. The crystalline polyester resin in the powder adhesive may separate from the thermoplastic resin when melted, but the presence of a polyvalent metal compound can suppress the separation of the crystalline polyester resin, thereby preventing the crystalline polyester resin from seeping out to the back side of the paper due to the crystalline polyester resin having separated from the thermoplastic resin permeating the paper. The content of the polyvalent metal compound in the powder adhesive is preferably 0.01% by mass or more and 1.0% by mass or less. The content of the polyvalent metal compound can be controlled by the amount of the polyvalent metal compound added to the powder adhesive or the manufacturing conditions of the powder adhesive.
[0044] The toner or powder adhesive may contain known materials, such as wax, charge control agents, charge control resins, pigment dispersants, etc., as necessary. The manufacturing method of the toner and the powder adhesive will be described. The manufacturing method of the toner particles and the powder adhesive particles can be a known method, and a kneading and grinding method or a wet manufacturing method can be used. From the viewpoint of uniformity of the particle size and shape controllability, the wet manufacturing method can be preferably used. Furthermore, the wet manufacturing method can include a suspension polymerization method, a dissolution suspension method, an emulsion polymerization aggregation method, an emulsion aggregation method, etc., and the emulsion aggregation method can be preferably used.
[0045] In the emulsion aggregation method, first, fine particles of a binder resin and, if necessary, fine particles of other materials such as a colorant are dispersed and mixed in an aqueous medium. A dispersion stabilizer or a surfactant may be added to the aqueous medium. Then, an aggregating agent is added to aggregate the particles to a desired particle size, and then or simultaneously with the aggregation, the resin fine particles are fused together. If necessary, the shape is controlled by heat to form toner particles and powder adhesive particles. Here, the binder resin particles can be composite particles formed of two or more layers made of resins with different compositions. For example, they can be produced by emulsion polymerization, mini-emulsion polymerization, phase inversion emulsification, or a combination of several production methods.
[0046] When the internal additive is contained in the toner particles and the powder adhesive particles, the internal additive may be contained in the resin fine particles, or a dispersion liquid of internal additive fine particles consisting of only the internal additive may be separately prepared and the internal additive fine particles may be aggregated together with the resin fine particles when the resin fine particles are aggregated. Also, by adding resin fine particles having different compositions at different times during aggregation and aggregating them, toner particles and powder adhesive particles having layer structures with different compositions can be produced.
[0047] The following can be used as the dispersion stabilizer: Inorganic dispersion stabilizers include tricalcium phosphate, magnesium phosphate, zinc phosphate, aluminum phosphate, calcium carbonate, magnesium carbonate, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, calcium metasilicate, calcium sulfate, barium sulfate, bentonite, silica, and alumina. Examples of the organic dispersion stabilizer include polyvinyl alcohol, gelatin, methyl cellulose, methylhydroxypropyl cellulose, ethyl cellulose, sodium salt of carboxymethyl cellulose, and starch.
[0048] As the surfactant, a known cationic surfactant, anionic surfactant, or nonionic surfactant can be used. Specific examples of the cationic surfactant include dodecyl ammonium bromide, dodecyl trimethyl ammonium bromide, dodecyl pyridinium chloride, dodecyl pyridinium bromide, and hexadecyl trimethyl ammonium bromide. Specific examples of the nonionic surfactant include dodecyl polyoxyethylene ether, hexadecyl polyoxyethylene ether, nonylphenyl polyoxyethylene ether, lauryl polyoxyethylene ether, and sorbitan monooleate polyoxyethylene ether. ether, styrylphenyl polyoxyethylene ether, monodecanoyl sucrose, etc. Specific examples of anionic surfactants include aliphatic soaps such as sodium stearate and sodium laurate, sodium lauryl sulfate, sodium dodecylbenzenesulfonate, and sodium polyoxyethylene (2) lauryl ether sulfate.
[0049] Examples of the flocculant include inorganic metal salts and polyvalent metal compounds having a valence of 2 or more. When a surfactant is used as an auxiliary in the microparticle dispersion, it is also effective to use a surfactant of the opposite polarity. In particular, when a polyvalent metal compound is used as the flocculant, the amount of surfactant used is reduced and the charging characteristics are improved. Examples of inorganic metal salts include metal salts such as sodium chloride, calcium chloride, calcium nitrate, barium chloride, magnesium chloride, magnesium sulfate, zinc chloride, aluminum chloride, aluminum sulfate, and iron chloride, as well as inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide.
[0050] If necessary, an external additive may be mixed into the toner particles or powder adhesive and adhered to the surface thereof. The powder adhesive preferably has inorganic fine particles A on its surface. The inorganic fine particles A are preferably silica fine particles. The silica fine particles are not particularly limited, and known silica such as sol-gel silica can be used. The number-average diameter of the primary particles of the inorganic fine particles A is preferably 30 nm or more and 200 nm or less, and more preferably 40 nm or more and 190 nm or less. When the powder adhesive has such inorganic fine particles A on its surface, curling of the product obtained by bonding two pieces of paper together during fixing can be suppressed. When the powder adhesive having inorganic fine particles A on its surface passes through a fixing unit, the inorganic fine particles A are dispersed in the adhesive part. When inorganic fine particles A are dispersed in resins such as thermoplastic resins and crystalline polyester resins, the filler effect makes it difficult for the resin to elastically deform, and curling of the finished product can be suppressed.
[0051] Furthermore, the powder adhesive has the effect of improving adhesive strength when it has inorganic fine particles A on its surface. The crystalline polyester resin in the powder adhesive is present in a finely dispersed state within the powder adhesive particles. When the powder adhesive melts, the finely dispersed crystalline polyester resin tends to maintain a favorable finely dispersed state with the inorganic fine particles A as cores. As a result, the viscosity of the thermoplastic resin in the powder adhesive as a whole can be uniformly reduced, making it easier for the resin to penetrate into the paper fibers and improving adhesive strength. The content of the inorganic fine particles A in the powder adhesive is preferably 0.05% by mass to 5.00% by mass.
[0052] The powder adhesive preferably has fine particles B on its surface. The fine particles B have a volume resistivity of 5.0×10 Ωm to 1.0×10 8 Preferably, it is 1.0×10 4 Ωm~1.0×10 7 It is more preferable that it is Ωm. The powder adhesive is transferred to the paper by the force of electrostatic charge during the transfer process. Therefore, the powder adhesive transferred to the paper is in an electrostatic state. If fine particles B are present on the surface of the powder adhesive, the electrostatic charge after the transfer process can be quickly alleviated. The electrostatic cohesion between the powder adhesive particles is also improved by the alleviation of the electrostatic charge, and the powder adhesive particles can easily penetrate instantly into the paper fibers when pressure is applied from the fixing device during the fixing process. As a result, the adhesive strength can be increased.
[0053] Fine particles B include iron oxide fine particles, titanium oxide fine particles, tin oxide fine particles, and zinc oxide fine particles. These particles include aluminum oxide particles, strontium titanate particles, barium titanate particles, and silicone particles. These particles alone have a volume resistivity of 5.0×10 Ωm to 1.0×10 8 Even if the material is not within the range of Ωm, the volume resistivity may be adjusted by forming a composite using two or more materials selected in any combination.
[0054] The fine particles B are preferably at least one selected from the group consisting of strontium titanate fine particles, titanium oxide fine particles, and silicone fine particles. The number average particle size (D1) of the primary particles of the fine particles B is preferably 10 nm or more and 500 nm or less, and more preferably 10 nm or more and 80 nm or less. The content of fine particles B in the powder adhesive is preferably 0.01% by mass to 5.00% by mass.
[0055] A flowability improver other than the inorganic fine particles A and the inorganic fine particles B may be added to the toner and the powder adhesive in order to improve the flowability and chargeability. The flowability improver preferably has a number-average particle size of 5 nm or more and 30 nm or less of primary particles, since this can provide high electrostatic chargeability and flowability. The flowability improver is preferably silica fine particles. The content of the flowability improver in the powder adhesive is preferably 0.01% by mass to 5.00% by mass. The content of the external additive in the toner is preferably 0.01% by mass to 5.00% by mass. The difference between the content of the external additive in the toner and the content of the external additive in the powder adhesive is preferably 0.0% by mass or more and 2.5% by mass or less, and more preferably 0.0% by mass or more and 2.0% by mass or less.
[0056] The average circularity of the powder adhesive is preferably 0.940 or more, and more preferably 0.970 or more. When the average circularity of the powder adhesive is 0.940 or more, the powder adhesive particles have a shape that makes them easy to roll, so that they easily penetrate into the paper fibers during the transfer process. As a result, the powder adhesive can melt while still inside the paper fibers, and the adhesive strength can be increased. The upper limit of the average circularity of the powder adhesive is not particularly limited, but is preferably 0.995 or less, and more preferably 0.990 or less. The average circularity of the powder adhesive can be controlled by the manufacturing conditions of the powder adhesive.
[0057] The weight average particle diameter (D4) of the toner is preferably 4.0 μm or more and 20.0 μm or less. By being in the above range, the melting state in the adhesion process can be made uniform, and therefore the high-temperature offset resistance is improved. The powder adhesive preferably has a weight average particle size (D4) of 3.0 μm or more and 17.0 μm or less. By being in this range, the powder adhesive can easily penetrate into the paper fibers during the bonding process, thereby obtaining sufficient adhesive strength. The weight average particle size (D4) of the toner and powder adhesive can be controlled by the manufacturing conditions of the toner and powder adhesive.
[0058] An example of an image forming apparatus and a processing apparatus for performing adhesive processing on paper, in which an electrophotographic developer containing a toner and a powdery adhesive can be suitably used, will be specifically described below. (Overall device configuration) First, the overall configuration of the image forming apparatus will be described with reference to Figs. 1, 2 and 5. Fig. 1 is a schematic diagram showing the cross-sectional configuration of an image forming apparatus 1 equipped with an image forming apparatus main body (hereinafter referred to as apparatus main body 10) and a post-processing unit 30 connected to the apparatus main body 10. The image forming apparatus 1 is equipped with the apparatus main body 10 equipped with an electrophotographic printing mechanism and a post-processing unit 30 serving as a sheet processing apparatus. The electrophotographic image forming apparatus (electrophotographic system) is constituted by the processing unit 30.
[0059] 5 is a perspective view showing the external appearance of the image forming apparatus 1. The post-processing unit 30 is attached to the upper part of the apparatus main body 10. The image forming apparatus 1 has a sheet cassette 8 at the bottom, an openable and closable tray 20 on the right side surface, and a first discharge tray 13 on the top surface. First, the internal configuration of the device main body 10 will be described. As shown in Fig. 1, the device main body 10 includes a sheet cassette 8 as a sheet storage section for storing sheets P as recording media, an image forming unit 1e as an image forming means, a first fixing device 6 as a fixing means, and a housing 19 for accommodating these. The device main body 10 has a printing function for forming a toner image on a sheet P fed from the sheet cassette 8 by the image forming unit 1e, and creating a printed matter by performing a fixing process by the first fixing device 6.
[0060] The sheet cassette 8 is inserted into the housing 19 at the bottom of the device main body 10 so as to be removable, and stores a large number of sheets P. The sheets P stored in the sheet cassette 8 are fed from the sheet cassette 8 by a feeding member such as a feeding roller, and are separated one by one by a pair of separation rollers and then transported by a transport roller 8a. It is also possible to feed sheets set in an open tray 20 (FIG. 5) one by one.
[0061] The image forming unit 1e is a tandem-type electrophotographic unit equipped with four process cartridges 7n, 7y, 7m, and 7c, a scanner unit 2, and a transfer unit 3. A process cartridge is a unit in which multiple parts responsible for an image forming process are integrated into one unit that can be replaced. The apparatus main body 10 is provided with a cartridge support part 9 supported by a housing 19, and the process cartridges 7n, 7y, 7m, 7c are detachably mounted in mounting parts 9n, 9y, 9m, 9c provided on the cartridge support part 9. The cartridge support part 9 may be a tray member that can be pulled out from the housing 19.
[0062] Each of the process cartridges 7n, 7y, 7m, and 7c has a substantially common configuration except for the type of powder contained in the four powder containers 104n, 104y, 104m, and 104c. That is, each of the process cartridges 7n, 7y, 7m, and 7c includes a photosensitive drum 101 as an image carrier, a charging roller 102 as a charger, a powder container 104n, 104y, 104m, and 104c that contains the powder, and a developing roller 105 that performs development using the powder.
[0063] Of the four powder containers, the three powder containers 104y, 104m, and 104c on the right side in the drawing contain yellow, magenta, and cyan printing toners Ty, Tm, and Tc, respectively, as toners (first powders) for forming a visible image on the sheet P. In contrast, the powder container 104n on the leftmost side in the drawing contains powder adhesive Tn, which is a powder (second powder) for performing an adhesion process after printing. The powder containers 104y, 104m, and 104c are all examples of a first container that contains printing toner, and the powder container 104n is an example of a second container that contains powder adhesive. The process cartridges 7y, 7m, and 7c are all examples of a first process unit that forms a toner image using printing toner, and the process cartridge 7n is an example of a second process unit that forms an image of powder adhesive in a predetermined application pattern.
[0064] When printing black images such as text, the process black is produced by superimposing yellow (Ty), magenta (Tm), and cyan (Tc) toners. However, for example, a fifth process cartridge using black printing toner may be added to the image forming unit 1e so that black images can be produced using black printing toner. However, the present invention is not limited to this, and the type and number of printing toners can be changed depending on the application of the image forming device 1. The scanner unit 2 is disposed below the process cartridges 7n, 7y, 7m, and 7c and above the sheet cassette 8. The scanner unit 2 is an exposure unit that irradiates the photosensitive drum 101 of each of the process cartridges 7n, 7y, 7m, and 7c with laser light G to write an electrostatic latent image thereon.
[0065] The transfer unit 3 includes a transfer belt 3a as an intermediate transfer body (secondary image carrier). The transfer belt 3a is a belt member wound around a secondary transfer inner roller 3b and a tension roller 3c, and its outer circumferential surface faces the photosensitive drums 101 of the process cartridges 7n, 7y, 7m, and 7c. On the inner circumferential side of the transfer belt 3a, a primary transfer roller 4 is disposed at a position corresponding to each photosensitive drum 101. In addition, a secondary transfer roller 5 as a transfer means is disposed at a position facing the secondary transfer inner roller 3b. A transfer nip 5n between the secondary transfer roller 5 and the transfer belt 3a is a transfer portion (secondary transfer portion) where a toner image is transferred from the transfer belt 3a to the sheet P.
[0066] The first fixing device 6 is disposed above the secondary transfer roller 5. The first fixing device 6 is a thermal fixing type fixing device having a heating roller 6a as a fixing member and a pressure roller 6b as a pressure member. The heating roller 6a is heated by a heating element such as a halogen lamp or a ceramic heater or a heating mechanism of an induction heating type. The pressure roller 6b is pressed against the heating roller 6a by a biasing member such as a spring, and generates a pressure force for applying pressure to the sheet P passing through a nip portion (fixing nip 6n) between the heating roller 6a and the pressure roller 6b.
[0067] The housing 19 is provided with a discharge port 12 (first discharge port) which is an opening for discharging the sheet P from the device body 10, and a discharge unit 34 is disposed in the discharge port 12. The discharge unit 34 which is a discharge means uses a so-called triple roller set having a first discharge roller 34a, an intermediate roller 34b, and a second discharge roller 34c. In addition, a switching guide 33, which is a flap-shaped guide that switches the transport path of the sheet P, is provided between the first fixing device 6 and the discharge unit 34. The switching guide 33 is rotatable around a shaft portion 33a such that a tip end 33b reciprocates in the direction of the arrow c in the figure.
[0068] The device main body 10 is equipped with a mechanism for performing double-sided printing. A motor (not shown) is connected to the discharge unit 34, and the intermediate roller 34b can rotate in the forward and reverse directions. A double-sided conveying path 1r is provided as a conveying path connected in a loop to the main conveying path 1m. The sheet P having an image formed on its first side while passing through the main conveying path 1m is sandwiched and conveyed between the first discharge roller 34a and the intermediate roller 34b by the switching guide 33 which has rotated clockwise. After the trailing end of the sheet P in the traveling direction passes through the switching guide 33, the switching guide 33 rotates counterclockwise and the intermediate roller 34b rotates in the reverse direction, so that the sheet P is inverted and conveyed to the double-sided conveying path 1r. Then, while the sheet P passes through the main conveying path 1m again in an inverted state, an image is formed on the second side of the sheet P.
[0069] After double-sided printing, the sheet P is nipped and conveyed between the intermediate roller 34b and the second discharge roller 34c by the switching guide 33 which has rotated counterclockwise, and is discharged from the apparatus main body 10. In the apparatus body 10, a transport path passing through the transport roller 8a, the transfer nip 5n, and the fixing nip 6n constitutes a main transport path 1m along which an image is formed on the sheet P. When viewed from the main scanning direction during image formation (the width direction of the sheet perpendicular to the transport direction of the sheet transported along the main transport path 1m), the main transport path 1m extends from below to above, passing along one side in the horizontal direction with respect to the image forming unit 1e. In other words, the device body 10 is a so-called vertical conveyance type (vertical path type) printer in which the main conveyance path 1m extends in a substantially vertical direction. The intermediate path 15 and the sheet cassette 8 overlap each other. Therefore, the movement direction of the sheet P when the discharge unit 34 discharges the sheet P in the horizontal direction is opposite to the movement direction of the sheet P when the sheet P is fed from the sheet cassette 8 in the horizontal direction.
[0070] 1 (when viewed in the main scanning direction during image formation), it is preferable that the horizontal occupancy area of the main body portion of the post-processing unit 30 excluding the second discharge tray 35 is within the occupancy area of the device main body 10. By accommodating the post-processing unit 30 in the space above the device main body 10 in this way, it becomes possible to install the image forming device 1 with adhesive printing function in an installation space approximately the same as that of a normal vertical pass printer.
[0071] (Gluing unit) 2, the post-processing unit 30 is attached to the upper part of the apparatus body 10. The post-processing unit 30 is a post-processing unit in which a folder 31 as a folding means and a second fixing device 32 as an adhesive means (second fixing means) are housed and integrated in a housing (second housing) 39. The post-processing unit 30 is provided with a first discharge tray 13 that rotatably holds a tray switching guide 13a, an intermediate path 15, and a second discharge tray 35. The first discharge tray 13 is provided on the upper surface of the post-processing unit 30 and is located on the upper surface (FIG. 1) of the entire image forming apparatus 1. The function of each part of the post-processing unit 30 will be described later.
[0072] The post-processing unit 30 is provided with a positioning portion (e.g., a convex shape that engages with a concave portion of the housing 19) for positioning the housing 39 relative to the housing 19 (first housing) of the device body 10. The post-processing unit 30 is also provided with a drive source and control unit separate from the device body 10, and is electrically connected to the device body 10 by coupling a connector 36 of the post-processing unit 30 with a connector 37 of the device body 10. This causes the post-processing unit 30 to enter a state in which it operates based on commands from the control unit provided in the device body 10, using power supplied via the device body 10.
[0073] (Process cartridge) As described above, each of the process cartridges 7n, 7y, 7m, and 7c has a substantially common configuration, except for the type of powder contained in each of the four powder containers 104n, 104y, 104m, and 104c. Here, the process cartridge 7n will be described as a representative. FIG. 7 is a schematic cross-sectional view of the process cartridge 7n. The process cartridge 7n is made up of a photosensitive unit CC including a photosensitive drum 101 and the like, and a developing unit DT including a developing roller 105 and the like.
[0074] A photosensitive drum 101 is rotatably attached to the photosensitive unit CC via a bearing (not shown). The photosensitive drum 101 is driven to rotate in a clockwise direction (arrow w) in the drawing in response to an image forming operation by receiving a driving force from a driving motor serving as a driving means (driving source) (not shown). Furthermore, a charging roller 102 for charging the photosensitive drum 101 and a cleaning member 103 are arranged around the photosensitive drum 101 in the photosensitive unit CC. The developing unit DT is provided with a developing roller 105 as a developer carrier that rotates in a counterclockwise direction (arrow d) in the figure in contact with the photosensitive drum 101. The developing roller 105 and the photosensitive drum 101 each rotate such that their surfaces move in the same direction at the opposing portion (contact portion).
[0075] The developing unit DT is provided with a developer supply roller 106 (hereinafter, simply referred to as a "supply roller") as a developer supply member that rotates in a clockwise direction (arrow e) in the figure. The supply roller 106 and the developing roller 105 have their surfaces rotated in the same direction at the opposing portion (contact portion). Each rotates so that it moves in the opposite direction. The supply roller 106 supplies powder adhesive (printing toner in the case of the process cartridges 7y, 7m, and 7c) onto the developing roller 105, and also acts to peel off any powder adhesive (printing toner in the case of the process cartridges 7y, 7m, and 7c) remaining on the developing roller 105 from above the developing roller 105. In addition, the developing unit DT is provided with a developing blade 107 as a developer regulating member that regulates the layer thickness of the powder adhesive (printing toner in the case of the process cartridges 7y, 7m, and 7c) supplied onto the developing roller 105 by the supply roller 106.
[0076] The powder container 104n contains a powder adhesive (printing toner in the case of the process cartridges 7y, 7m, and 7c). A rotatably supported transport member 108 is provided in the powder container 104n. The stirring member 108 rotates in a clockwise direction (arrow f) in the drawing to stir the powder contained in the powder container 104n and transport the powder to a development chamber 109 in which the development roller 105 and the supply roller 106 are provided. Here, the photoconductor unit CC and the developing unit DT may be separately formed as a photoconductor unit cartridge and a developing unit cartridge, respectively, and may be configured to be detachable from the main body of the image forming apparatus. It is also possible to configure the device as a powder cartridge that has only the powder container 104 and the conveying member 108 and is detachable from the main body of the apparatus.
[0077] (Image formation operation) Next, the image forming operation performed by the image forming apparatus 1 will be described with reference to Figs. 1 to 7. Figs. 3(a) and 3(b) are diagrams showing the sheet transport path in the image forming apparatus 1. Figs. 4(a) to 4(f) are diagrams for explaining the contents of the folding process. Figs. 6(a) and 6(b) are diagrams showing examples of products output by the image forming apparatus 1. When data of an image to be printed and a command to execute printing are input to the image forming apparatus 1, the control unit of the image forming apparatus 1 starts a series of operations (image forming operations) of conveying a sheet P to form an image, and, if necessary, performing post-processing by the post-processing unit 30. In the image forming operation, first, as shown in Fig. 1, the sheets P are fed one by one from the sheet cassette 8 and conveyed toward the transfer nip 5n via the conveying roller 8a.
[0078] In parallel with the feeding of the sheet P, the process cartridges 7n, 7y, 7m, and 7c are sequentially driven, and the photosensitive drum 101 is rotated in the clockwise direction (arrow w) in the figure. At this time, the photosensitive drum 101 is uniformly charged on its surface by the charging roller 102. Further, the scanner unit 2 irradiates the photosensitive drum 101 of each of the process cartridges 7n, 7y, 7m, and 7c with laser light G modulated based on image data to form an electrostatic latent image on the surface of the photosensitive drum 101. Next, the electrostatic latent image on the photosensitive drum 101 is developed into a powder image by powder carried on the developing roller 105 of each of the process cartridges 7n, 7y, 7m, and 7c.
[0079] The powder adhesive layer formed on the photosensitive drum 101 by development with the powder adhesive Tn differs from a toner image (normal toner image) of printing toner for recording images such as figures and text on the sheet P in that it is not intended to transmit visual information. However, in the following description, in order to apply the powder adhesive Tn to the sheet P in a predetermined application pattern, the layer of powder adhesive Tn developed into a shape corresponding to the application pattern by the electrophotographic process will also be treated as one of the "toner images." The transfer belt 3a rotates in a counterclockwise direction (arrow v) in the figure. The toner images formed in the process cartridges 7n, 7y, 7m, and 7c are primarily transferred from the photosensitive drum 101 to the transfer belt 3a by an electric field formed between the photosensitive drum 101 and the primary transfer roller 4.
[0080] The toner image carried by the transfer belt 3a and reaching the transfer nip 5n is secondarily transferred onto the sheet P transported along the main transport path 1m by the electric field formed between the secondary transfer roller 5 and the secondary transfer inner roller 3b. Thereafter, the sheet P is conveyed to the first fixing device 6 and subjected to a thermal fixing process. That is, when the sheet P passes through the fixing nip 6n, the toner image on the sheet P is heated and pressurized, so that the printing toners Ty, Tm, Tc and the powder adhesive Tn melt and then solidify, thereby obtaining an image fixed on the sheet P.
[0081] Regardless of single-sided or double-sided printing, the sheet P discharged from the device body 10 is sandwiched between the intermediate roller 34b and the second discharge roller 34c, as shown in Figures 3(a) and 3(b), and is transported to the first path R1 or the second path R2 by the tray switching guide 13a. A first path R1 shown in FIG. 3(a) is a path along which the sheet P that has passed through the first fixing device 6 is discharged onto the first discharge tray 13 by the discharge unit 34 in a normal printing mode in which the post-processing unit 30 is not used. The second path R2 shown in Figure 3 (b) is a path along which, in the adhesive printing mode, the sheet P that has passed through the first fixing device 6 is discharged to the second discharge tray 35 via the discharge unit 34, the folder 31 and the second fixing device 32.
[0082] An intermediate path 15 is provided between the first fixing unit 6 and the folder 31 in the second route R2. The intermediate path 15 is a sheet transport path that passes through the upper surface (top surface) of the image forming apparatus 1, and extends below the first discharge tray 13 and substantially parallel to the first discharge tray 13. The intermediate path 15 and the first discharge tray 13 are inclined vertically upward toward the folder 31 with respect to the horizontal direction. Therefore, the entrance of the folder 31 (the guide roller pair (31c, 31d) described below) is located vertically above the exit of the device main body 10 (the nip between the intermediate roller 34b and the second discharge roller 34c). The folder 31 has four rollers, namely, a first guide roller 31c, a second guide roller 31d, a first folding roller 31a, and a second folding roller 31b, and a lead-in portion 31e. The first guide roller 31c and the second guide roller 31d are a pair of guide rollers that sandwich and transport the sheet P received from a transport path (intermediate path 15 in this embodiment) on the upstream side of the folder 31. The first folding roller 31a and the second folding roller 31b are a pair of folding rollers that feed the sheet P while folding it.
[0083] Note that the distance M (FIG. 1) between the second discharge roller 34c and the first guide roller 31c in the sheet transport direction along the second path R2 is configured to be shorter than the overall length L (FIG. 4(a)) in the transport direction of the sheet P before folding. In other words, the distance M between the second discharge roller 34c and the first guide roller 31c determines the lower limit of the length in the transport direction of the sheet that can be processed by the post-processing unit 30. With this configuration, the sheet P is smoothly delivered from the discharge unit 34 to the pair of guide rollers.
[0084] The folding process by folder 31 will be described with reference to Figures 4(a) to 4(f). When performing the folding process, first guide roller 31c and first folding roller 31a rotate clockwise in the figure, and second guide roller 31d and second folding roller 31b rotate counterclockwise in the figure. First, the leading edge q of the sheet P sent out from the discharge unit 34 is pulled into the pair of guide rollers (31c, 31d) as shown in Fig. 4(a). As shown in Fig. 4(b), the leading edge q of the sheet P is guided downward by the guide wall 31f, contacts the first folding roller 31a, is pulled into the mutually opposing first folding roller 31a and second guide roller 31d, and abuts against the wall 31g of the pull-in portion 31e.
[0085] As the sheet P is pulled in by the pair of guide rollers (31c, 31d), the leading end q advances to the inside of the pull-in portion 31e while being in sliding contact with the wall 31g. As shown in FIG. 4C, the sheet P hits the end 31h of the lead-in portion 31e. The lead-in portion 31e forms a space extending substantially parallel to the intermediate path 15 below the intermediate path 15, and the sheet P is wound around the second guide roller 31d and bent into a U-shape. When the sheet P is further drawn in by the guide roller pair (31c, 31d) from the state shown in Fig. 4(c), bending begins to occur at the middle portion r as shown in Fig. 4(d). Eventually, as shown in Fig. 4(e), the middle portion r comes into contact with the second folding roller 31b, and the sheet P is drawn into the nip portion of the folding roller pair (31a, 31b) by the frictional force received from the second folding roller 31b. Then, as shown in Fig. 4(f), the sheet P is folded with the middle portion r as the crease, and is discharged by the folding roller pair (31a, 31b) with the middle portion r at the front.
[0086] Here, the depth N of the retraction portion 31e (FIG. 4(e)), i.e., the distance from the nip portion of the pair of folding rollers (31a, 31b) to the end portion 31h of the retraction portion 31e, is set to half the total length L of the sheet P. This enables the folder 31 to fold the sheet P in half (center folding). Note that by changing the depth N of the retraction portion 31e, the position of the fold can be changed as desired. The folder 31 described above is an example of a folding means, and a folding mechanism may be used that forms a crease by pressing a blade against the sheet P and pushing it into a nip between a pair of rollers. The folding process is not limited to folding in half, and a folding mechanism that performs, for example, a Z-fold or a triple fold may be used. Since the folder 31 is composed of rotating rollers and a fixed retraction section 31e, the drive mechanism can be simplified compared to a folding mechanism that uses a reciprocating blade. Also, the folder 31 only needs to be provided with the retraction section 31e having a depth N that is half the sheet length in addition to the four rollers, so the post-processing unit 30 can be made compact.
[0087] The sheet P that has passed through the folder 31 is conveyed to the second fixing device 32 as shown in Fig. 3(b). The second fixing device 32 has a thermal fixing type configuration similar to the first fixing device 6. That is, the second fixing device 32 has a heating roller 32b as a heating member and a pressure roller 32a as a pressure member. The heating roller 32b is heated by a heating element such as a halogen lamp or a ceramic heater, or a heating mechanism of an induction heating type. The pressure roller 32a is pressed against the heating roller 32b by a biasing member such as a spring, and generates a pressure force for applying pressure to the sheet P passing through a nip portion (adhesion nip) between the heating roller 32b and the pressure roller 32a.
[0088] The sheet P folded by the folder 31 is subjected to a bonding process (a second thermal fixing to the image surface to which the powder adhesive Tn has been applied) by the second fixer 32, so that the sheet P is bonded in the folded state. That is, when the sheet P passes through the bonding nip, the powder adhesive Tn on the sheet P is heated and remelted, and is then pressurized, so that the powder adhesive Tn adheres to the opposing surface (the surface opposing the image surface of the sheet P to which the toner image of the powder adhesive Tn has been transferred in the folded state). Then, the powder adhesive Tn cools and hardens, so that the image surface and the opposing surface of the sheet P are bonded (bonded) together using the powder adhesive Tn as an adhesive.
[0089] The sheet P that has been subjected to the adhesion process by the second fixing device 32 is discharged to the left side in the figure from a discharge outlet 32c (second discharge outlet) provided in a housing 39 of the post-processing unit 30, as shown in Fig. 3(b). Then, the sheet P is stored in a second discharge tray 35 (see Fig. 1) provided on the left side surface of the apparatus main body 10. This completes the image formation operation when the sheet P is transported along the second path R2.
[0090] It is possible to change the bonding locations of the folded sheet P by changing the application pattern of the powder adhesive Tn on the sheet P. Figures 6(a) and 6(b) show examples of deliverables (output products of the image forming apparatus) with different application patterns of the powder adhesive Tn. Fig. 6(a) is an example of a deliverable (semi-adhesive deliverable) intended to be opened by the recipient. In the case of a pay slip 51 in Fig. 6(a), powder adhesive Tn is applied to the entire circumference 51a of the outer periphery on one side of a sheet P, and the sheet is folded and adhered at a central crease 51b. Fig. 6(b) shows a bag (medicine bag) as an example of a product (fully bonded product) that is not intended to be opened. In this case, powder adhesive Tn is applied to a U-shaped area 52a so that three sides, including crease 52b, of the folded sheet P are joined. Although no image is formed on the inside of the bag in Fig. 6(b), an image can be formed if necessary.
[0091] 6(a) and 6(b), the image forming apparatus 1 can output any of the products exemplified in Fig. 6(a) and 6(b) in one stop without preparing preprinted paper. That is, in parallel with the operation of recording an image on one or both sides of the sheet P using printing toner, it is possible to apply the powder adhesive Tn in a predetermined application pattern and output a product in a state in which the sheet has been subjected to folding and adhesive processing. 6(a) and 6(b), one side of the sheet P used as the base paper becomes the outside of the product, and the other side becomes the inside of the product. Therefore, in the image forming operation for the first side in double-sided printing, an image for the outside surface is formed with printing toner, and in the image forming operation for the second side, an image for the inside surface is formed with printing toner and powder adhesive Tn is applied in a predetermined application pattern.
[0092] The image recorded by the image forming device 1 using printing toner can include the format (unchanging portion) when preprinted paper is used, and variable portions such as personal information. Therefore, as described above, it is possible to output a product that is bonded by a gluing process from base paper such as blank paper that is not preprinted paper. However, the image forming device 1 can also be used for purposes in which preprinted paper is used as a recording medium and printing and gluing processes for variable portions are performed.
[0093] (Method of manufacturing adhesive (finished product)) A method for producing an adhesive product in which at least one piece of paper is bonded to the adhesive using the electrophotographic developer set, comprising the steps of: In the bonded object, a surface of the paper on which the adhesive portion exists is designated as surface A, and a surface other than surface A is designated as surface B. In the bonded object, at least one of surface B has an image area formed by the toner, The method for producing the adhesive product includes the steps of: a step of forming an image portion by developing the image portion with toner on at least one of the surfaces of the paper that will become the surface B and fixing the image portion by heating; and A bonding section forming step of developing the bonding section with a powder adhesive on at least one of the surfaces of the paper that will become the surface A and fixing the bonding section by heating. in any order, Further, the method for producing the bonded article further comprises the steps of: The method includes a bonding step in which the papers are stacked so as to sandwich the formed bonded portion, and heated to melt the bonded portion to bond the papers together, thereby obtaining the bonded product.
[0094] The bonded product may be in the form of a single piece of paper that is folded and bonded together via an adhesive part, or in the form of two pieces of paper that are bonded together via an adhesive part. The bonded product may have, for example, a bag-like or tubular shape. When papers are bonded together via an adhesive joint, there will be two surfaces A on which the adhesive joint exists in the bonded object, and the adhesive joint made of powder adhesive need only be formed on at least one of the two surfaces.
[0095] Similarly, when papers are pasted together through an adhesive, there are two surfaces in the bonded object, one being surface A where the adhesive exists, and the other being surface B, but the toner image is It is sufficient that the image portion is formed on at least one of the two surfaces. Also, it is sufficient that the image portion is formed on at least surface B, and the image portion may or may not be formed on surface A.
[0096] The order of the image forming process and the adhesive process is not limited. Either one may be performed first, or both may be performed simultaneously. The image forming process and the adhesive process may be performed, for example, by the image forming apparatus described above. A known electrophotographic method may also be used. When two sheets of paper are pasted together, the image and the adhesive may be formed on one of the sheets, or on both of the sheets. When the paper is one sheet, the adhesive portion is formed on one side of the paper, and the image portion is formed on at least the other side.
[0097] After forming the image area and adhesive area, if it is one piece of paper, the paper is folded to sandwich the adhesive area, and if it is two pieces of paper, they are stacked and the adhesive area is sandwiched. Then, the adhesive area is melted by heating to bond the papers together, and an adhesive product (delivered product) is obtained. Such an adhesive process can be performed, for example, using the image forming apparatus or sheet processing apparatus described above.
[0098] The measurement methods for each physical property are described below. <Identification of the molecular structures of thermoplastic resins and crystalline polyester resins, and methods for measuring the content of crystalline polyester resins in toners and powder adhesives, and the content of thermoplastic resins in powder adhesives> A pyrolysis gas chromatography mass spectrometer (hereafter referred to as pyrolysis GC / MS) and NMR are used to identify the molecular structures of the thermoplastic resin and the crystalline polyester resin, and to measure the amount of crystalline polyester resin contained in the toner and powder adhesive, and the amount of crystalline polyester resin contained in the powder adhesive. Pyrolysis GC / MS can determine the constituent monomers of the entire resin sample and calculate the peak area of each monomer, but quantification requires normalization of peak intensity using a reference sample of known concentration.On the other hand, NMR makes it possible to determine and quantify the constituent monomers without using a sample of known concentration. Therefore, depending on the circumstances, the constituent monomers are determined by comparing the spectra obtained by both NMR and pyrolysis GC / MS.
[0099] Specifically, when the amount of resin components that are insoluble in deuterated chloroform, which is the extraction solvent used in NMR measurement, is less than 5.0% by mass, quantification is performed by NMR measurement. On the other hand, when 5.0% by mass or more of resin components that are insoluble in deuterated chloroform, which is the extraction solvent used in NMR measurement, are present, both NMR and pyrolysis GC / MS measurements are performed on the deuterated chloroform soluble fraction, and pyrolysis GC / MS measurement is performed on the deuterated chloroform insoluble fraction. In this case, first, NMR measurement is performed on the deuterated chloroform soluble fraction to determine and quantify the constituent monomers (quantitative result 1). Next, pyrolysis GC / MS measurement is performed on the deuterated chloroform soluble fraction to determine the peak area of the peak attributable to each constituent monomer. Using quantitative result 1 obtained by NMR measurement, the relationship between the amount of each constituent monomer and the pyrolysis GC / MS peak area is determined. Next, the deuterated chloroform insoluble fraction is subjected to pyrolysis GC / MS measurement to determine the peak area of the peak attributable to each constituent monomer. From the relationship between the amount of each constituent monomer obtained by the measurement of the deuterated chloroform soluble fraction and the peak area of the pyrolysis GC / MS, the constituent monomers in the deuterated chloroform insoluble fraction are quantified (quantitative result 2). Then, the quantitative result 1 and the quantitative result 2 are combined to obtain the final quantitative result of each constituent monomer. Specifically, the following operations are carried out.
[0100] (1) 50 mg of toner or powder adhesive was precisely weighed into an 8 mL glass sample bottle and deuterated. After adding 1 mL of chloroform, the container is closed and dispersed and dissolved for 1 hour using an ultrasonic disperser. The mixture is then filtered through a 0.4 μm membrane filter and the filtrate is collected. At this time, the deuterated chloroform insoluble matter remains on the membrane filter. (2) Regarding the filtrate: 1 H-NMR measurement is performed, and the spectrum is assigned to each constituent monomer in the resin to obtain a quantitative value. (3) If analysis of deuterium chloroform insoluble matter is required, perform pyrolysis GC / MS analysis. If necessary, perform derivatization such as methylation.
[0101] (NMR measurement conditions) Bruker AVANCE 500 manufactured by Bruker Biospin Co., Ltd. Measurement nuclei: 1 H Measurement frequency: 500.1MHz Number of times: 16 Measurement temperature: room temperature
[0102] (Measurement conditions for pyrolysis GC / MS) Pyrolysis equipment: Japan Analytical Industry Co., Ltd. TPS-700 Thermal decomposition temperature: Optimum value between 400℃ and 600℃ GC / MS equipment: ISQ manufactured by Thermo Fisher Scientific Co., Ltd. Column: "HP5-MS" (Agilent / 19091S-433), length 30 m, inner diameter 0.25 mm, film thickness 0.25 μm GC / MS conditions Filler requirements: InletTemp:250℃ Split Flow: 50mL / min GC heating conditions: 40℃ (5min) → 10℃ / min (300℃) → 300℃ (20min)
[0103] <Method for measuring the glass transition temperature (Tg) of thermoplastic resin> The glass transition temperature (Tg) of the thermoplastic resin is measured using a differential scanning calorimeter "Q1000" (manufactured by TA Instruments). The melting points of indium and zinc are used for temperature correction of the detector, and the heat of fusion of indium is used for heat correction. Specifically, 1 mg of sample is weighed out and placed in an aluminum pan, and an empty aluminum pan is used as a reference. Using the modulation measurement mode, measurements are performed in the range of 0°C to 100°C with a temperature rise rate of 1°C / min and temperature modulation conditions of ±0.6°C / 60 seconds. Since the specific heat change is obtained during the temperature rise process, the intersection point between the line midway between the baseline before and after the specific heat change and the differential heat curve is taken as the glass transition temperature (Tg).
[0104] <Method for measuring weight-average particle size (D4) of powder adhesives and toners> The weight average particle diameter (D4) is calculated as follows. The measurement device used is a precision particle size distribution measurement device using the pore electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube. The measurement conditions are set and the measurement data is analyzed using the accompanying dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.). The measurement is performed with an effective measurement channel count of 25,000. The electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of 1.0%, for example, "ISOTON II" (manufactured by Beckman Coulter, Inc.). Before performing measurements and analysis, the dedicated software is set up as follows. In the "Change standard measurement method (SOMME)" screen of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard particle 10.0 μm" (Beckman Coulter, Inc.). Press the "Threshold / Noise level measurement button" to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check "Flush aperture tube after measurement." In the "Pulse to particle size conversion setting" screen of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range to 2 μm to 60 μm.
[0105] The specific measurement method is as follows. (1) Pour 200.0 mL of the electrolyte solution into a 250 mL round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "Aperture tube flush" function of the dedicated software to remove dirt and air bubbles from inside the aperture tube. (2) Place 30.0 mL of the electrolyte solution in a 100 mL flat-bottom glass beaker. Add 0.3 mL of a solution of "Contaminon N" (a 10% aqueous solution of a neutral detergent for cleaning precision measuring instruments with a pH of 7, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) diluted 3 times by mass with ion-exchanged water as a dispersant. (3) Prepare an ultrasonic disperser "Ultrasonic Dispersion System Tetra150" (manufactured by Nikkaki Bios Co., Ltd.) that has two built-in oscillators with an oscillation frequency of 50 kHz and a phase shift of 180 degrees and an electrical output of 120 W. Place 3.3 L of ion-exchanged water in the ultrasonic disperser's water tank and add 2.0 mL of Contaminon N to this tank. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, 10 mg of the measurement sample is added little by little to the electrolyte solution and dispersed. Then, the ultrasonic dispersion process is continued for another 60 seconds. During the ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) Using a pipette, the electrolyte solution (5) in which the toner particles are dispersed is dropped into the round-bottom beaker (1) placed in the sample stand, and the measurement concentration is adjusted to 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) Analyze the measurement data using the dedicated software that comes with the device to calculate the weight-average particle size (D4). Note that when the dedicated software is set to Graph / Volume%, the "Average diameter" on the "Analysis / Volume Statistics (Arithmetic Mean)" screen is the weight-average particle size (D4).
[0106] <Method of measuring storage modulus and tan δ of toner and powder adhesive> The measurement is carried out using a dynamic viscoelasticity measuring device (rheometer) ARES (manufactured by Rheometrics Scientific Co., Ltd.) Toner or powder adhesive is used as a sample. Measurement jig: A serrated parallel plate with a diameter of 7.9 mm was used. Measurement sample: Using a pressure molding machine, mold a 1.0 g sample into a cylindrical sample with a diameter of about 8 mm and a height of about 2 mm (maintain 15 kN for 1 minute at room temperature). The pressure molding machine used is a 100 kN press NT-100H manufactured by NPa Systems. The temperature of the serrated parallel plate is adjusted to 120°C, the cylindrical sample is heated and melted, the sawtooth is inserted, and a load is applied in the vertical direction so that the axial force does not exceed 30 (gf) (0.294N) to fix it to the serrated parallel plate. At this time, a steel belt may be used so that the diameter of the sample is the same as that of the parallel plate. The serrated parallel plate is heated to a measurement start temperature of 30.00°C over one hour. The cylindrical sample is then slowly cooled. Measurement frequency: 6.28 rad / sec Measurement distortion setting: Set the initial value to 0.1%, and perform the measurement in automatic measurement mode. Sample elongation correction: Adjusted in automatic measurement mode. Measurement temperature: 30°C to 180°C at a rate of 2°C per minute. Measurement interval: Measure viscoelastic data every 30 seconds, i.e., every 1°C. From the storage modulus curve obtained by this measurement, Gb'(100), Tb, and tan δ of the powder adhesive, and Gt'(100) and Tt of the toner are obtained.
[0107] <Measuring method for melting point of crystalline polyester resin> The melting point of the crystalline polyester resin used in the toner and powder adhesive is DSC Q100. Measurements are performed using a TA Instruments 0 under the following conditions. Heating rate: 10℃ / min Measurement start temperature: 20℃ End of measurement temperature: 180℃ The melting points of indium and zinc are used for temperature correction of the device detection section, and the heat of fusion of indium is used for heat correction. Specifically, 5 mg of a sample is weighed out and placed in an aluminum pan, and differential scanning calorimetry is performed using an empty silver pan as a reference. The peak temperature of the maximum endothermic peak in the first heating process is taken as the melting point. The maximum endothermic peak refers to the peak with the largest amount of endothermic heat when there are multiple peaks.
[0108] (Isolation of Crystalline Polyester Resin from Toner or Powder Adhesive) The physical properties can also be measured by the following method using the crystalline polyester resin isolated from the toner or powder adhesive. The toner or powder adhesive is dispersed in ethanol, which is a poor solvent for the toner or powder adhesive, and the temperature is raised to a temperature exceeding the melting point of the crystalline polyester resin. At this time, pressure may be applied if necessary. At this point, the crystalline polyester resin, which has exceeded its melting point, is melted. Then, the crystalline polyester resin can be extracted from the toner or powder adhesive by solid-liquid separation. If the separated crystalline material is a mixture, the mixture can be classified according to molecular weight to isolate the crystalline polyester resin. The crystalline polyester resin can also be identified from the molecular structure of the crystalline material by the above-mentioned method.
[0109] <Method of measuring number average molecular weight Mn and weight average molecular weight Mw of thermoplastic resin and crystalline polyester resin> The molecular weights Mn and Mw of the thermoplastic resin and the crystalline polyester resin used in the toner and the powder adhesive are measured by gel permeation chromatography (GPC) as follows. First, the sample is dissolved in tetrahydrofuran (THF) at room temperature for 24 hours. The resulting solution is then filtered through a solvent-resistant membrane filter "Myshoridisc" (Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. The sample solution is adjusted so that the concentration of components soluble in THF is approximately 0.8 mass%. This sample solution is used to perform measurements under the following conditions. Equipment: HLC8120 GPC (detector: RI) (Tosoh Corporation) Column: Shodex KF-801, 802, 803, 804, 805, 806, 80 7 of 7 (manufactured by Showa Denko) Eluent: tetrahydrofuran (THF) Flow rate: 1.0ml / min Oven temperature: 40.0℃ Sample injection volume: 0.10 ml In calculating the molecular weight of the sample, a molecular weight calibration curve prepared using standard polystyrene resins (e.g., trade names "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500" manufactured by Tosoh Corporation) is used.
[0110] <Method for measuring the average circularity of powder adhesive> The average circularity of the powder adhesive is measured using a flow type particle image analyzer "FPIA-3000" (manufactured by Sysmex Corporation) under the measurement and analysis conditions at the time of calibration work. The specific measurement method is as follows. First, about 20 mL of ion-exchanged water from which impurities such as solids have been removed is placed in a glass container, and 0.2 mL of a solution of "Contaminon N" (a 10% aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments made from a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries) diluted about 3 times by mass with ion-exchanged water is added as a dispersant. Add approximately 0.02 g of the measurement sample and disperse it for 2 minutes using an ultrasonic disperser to obtain a dispersion for measurement. At this time, cool the dispersion appropriately so that the temperature is between 10°C and 40°C. As the ultrasonic disperser, a tabletop ultrasonic cleaner disperser (e.g., "VS-150" (manufactured by Vervoclear)) with an oscillation frequency of 50 kHz and an electrical output of 150 W is used, a predetermined amount of ion-exchanged water is placed in the water tank, and approximately 2 mL of the Contaminon N is added to this water tank. For the measurement, a flow type particle image analyzer equipped with a "LUCPLFLN" (magnification 20x, numerical aperture 0.40) objective lens is used, and a particle sheath "PSE-900A" (manufactured by Sysmex Corporation) is used as the sheath liquid. The dispersion liquid prepared according to the above procedure is introduced into the flow type particle image analyzer, and 2000 particles are measured in HPF measurement mode and total count mode. The binarization threshold for particle analysis is set to 85%, the particle diameters analyzed are limited to equivalent circle diameters of 1.977 μm or more and less than 39.54 μm, and the average circularity of the sample is determined. Before starting the measurement, automatic focus adjustment is performed using standard latex particles (e.g., Duke Scientific's "RESEARCH AND TEST PARTICLES Latex Microsphere Suspensions 5100A" diluted with ion-exchanged water). After that, it is preferable to perform focus adjustment every 2 hours from the start of the measurement. In the examples of the present application, a flow-type particle image analyzer that has been calibrated by Sysmex Corp. and has a calibration certificate issued by Sysmex Corp. is used. Measurements are performed under the same measurement and analysis conditions as when the calibration certificate was received, except that the particle diameter to be analyzed is limited to a circle equivalent diameter of 1.977 μm or more and less than 39.54 μm.
[0111] <Method for measuring number average particle size of primary particles of inorganic fine particles A and fine particles B> The number average particle size of the primary particles of the inorganic fine particles A and the fine particles B is measured using a transmission electron microscope "JEM-2800" (JEOL Ltd.). The powder adhesive to which inorganic fine particles A and B have been added is observed, and the number-average particle size is calculated by measuring the major axis of the primary particles of 100 randomly selected inorganic fine particles A and B in a field of view magnified up to 200,000 times. The observation magnification can be adjusted appropriately depending on the size of inorganic fine particles A and B.
[0112] The means for distinguishing the inorganic fine particles A and the fine particles B from other inorganic fine particles on the surface of the powder adhesive is as follows. Powder adhesive is ultrasonically dispersed in methanol to obtain inorganic fine particles A and B, as well as other fine particles. The inorganic fine particles are removed and allowed to stand for 24 hours. The settled powder adhesive particles are separated from the inorganic fine particles A and B dispersed in the supernatant, as well as other inorganic fine particles. The supernatant can then be separated by centrifugation to isolate the inorganic fine particles A and B, as well as other inorganic fine particles. The isolated inorganic fine particles A and B, as well as other inorganic fine particles, are subjected to TEM-EDX and morphological analysis, and the fine particles are differentiated based on the analytical results obtained, after which the particle diameters are measured by the above-mentioned transmission electron microscope observation.
[0113] <Method for measuring volume resistivity of fine particles B> The volume resistivity of the fine particles B is measured in an environment of 25° C. as follows. The equipment used is a Keithley Instruments 6517 Electrometer / High Resistance System. Electrodes with a diameter of 25 mm are connected, and a sample is placed between the electrodes to a thickness of 0.5 mm. The distance between the electrodes is measured with a load of approximately 2.0 N (approximately 204 g) applied. A voltage of 1,000 V is applied to the fine particle B for 1 minute, the resistance value is measured, and the volume resistivity is calculated using the following formula. Volume resistivity (Ω cm)=R×L R: Resistance value (Ω) L: Distance between electrodes (cm) (Isolation of Microparticle B from Powder Adhesive) The fine particles B isolated from the powder adhesive by the above method can also be used to measure various physical properties.
[0114] <Method for measuring the content of polyvalent metal elements in powder adhesives> The content of polyvalent metal elements in the powder adhesive is determined by an inductively coupled plasma atomic emission spectrometer (ICP-AES (manufactured by Seiko Instruments Inc.)). As a pretreatment, 100.0 mg of the powder adhesive is subjected to acid decomposition using 8.00 ml of 60% nitric acid (manufactured by Kanto Chemical, for atomic absorption spectrometry). During acid decomposition, the sample is treated in a sealed container at an internal temperature of 220° C. for 1 hour using a microwave high-power sample pretreatment device ETHOS1600 (Milestone General Co., Ltd.) to prepare a solution sample containing polyvalent metal elements. Then, add ultrapure water to make the total amount 50.00g to prepare the measurement sample. A calibration curve is created for each polyvalent metal element, and the amount of metal contained in each sample is quantified. Note that 8.00ml of nitric acid is added with ultrapure water to make a total of 50.00g, which is used as a blank, and the amount of metal in the blank is subtracted.
[0115] <Method for measuring colorant content in powder adhesive> The content of colorant in the powder adhesive is quantified using ultraviolet-visible absorption spectroscopy. A square spacer 1 mm thick is placed on a glass slide, 50 mg of powder adhesive is placed on it, and it is heated to 120°C to 180°C on a hot plate to melt it. Then, the glass slide is placed on the spacer, sandwiched between the spacers, and cooled. After checking that there are no air bubbles or other inclusions, the content is measured using an ultraviolet-visible spectrophotometer. When crystalline materials such as wax are included and quantitative determination is difficult due to the crystalline portions, separate samples shall be prepared for the THF-soluble and THF-insoluble portions of the powder adhesive and measurements shall be performed. The THF-insoluble portion of the powder adhesive is obtained by the following procedure. 500 mg of powder adhesive is placed in a cylindrical filter paper (product name: No. 86R, size 28 x 100 mm, manufactured by Advantec Toyo Co., Ltd.) and set in a Soxhlet extractor. Extraction is performed for 18 hours using 200 mL of THF as the solvent, with the reflux speed set so that the solvent extraction cycle occurs approximately once every 5 minutes. After extraction is complete, the cylindrical filter paper is removed and air-dried, and then vacuum-dried at 40°C for 8 hours, and the extraction residue is obtained as the THF-insoluble portion. The THF soluble content of the powder adhesive is measured by dissolving 50 mg of sample in 30 ml of THF and placing it in a 10 mm x 10 mm x 50 mm quartz cell. If sufficient absorbance is not obtained, adjust the amount of THF appropriately. For quantification, the structure of the colorant contained in the powder adhesive is identified in advance, and a calibration curve is created using the same compound separately to perform calibration. The method for preparing samples for creating a calibration curve is shown below.
[0116] Weigh out the following materials into a glass bottle and disperse them for 18 hours using a paint shaker. Colorant: 5.00 parts by weight φ2mm zirconia beads: 70 parts by weight Toluene: 45.00 parts by mass The obtained dispersion is diluted with toluene to prepare samples of 100,000-fold dilution, 10,000-fold dilution, 1,000-fold dilution, and 100-fold dilution, and a calibration curve is obtained. The absorption spectrum of the obtained sample is measured using an ultraviolet-visible spectrophotometer (Shimadzu Corporation: UV-2600), and the colorant content in the powder adhesive is measured by quantifying the characteristic absorption wavelength of the colorant. EXAMPLES
[0117] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples, the parts are by weight unless otherwise specified. Hereinafter, Examples 21, 22, and 30 will be referred to as Reference Examples 21, 22, and 30, respectively.
[0118] <Production Example of Crystalline Polyester Resin 1> 1,10-Decanediol 183 parts Sebacic acid 230 parts Dibutyltin oxide 0.1 parts The above materials were placed in a heated and dried two-necked flask, and nitrogen gas was introduced into the container to maintain an inert atmosphere and raise the temperature while stirring. Then, stirring was performed for 6 hours at 170°C. After that, the temperature was gradually raised to 210-230°C under reduced pressure while continuing stirring, and was maintained until the desired molecular weight Mn was reached. When the mixture became viscous, it was air-cooled to stop the reaction, and crystalline polyester resin 1 was synthesized. The crystalline polyester resin 1 had a number average molecular weight (Mn) of 7200 and a melting point of 72°C.
[0119] <Production Examples of Crystalline Polyester Resins 2 to 9> Crystalline polyester resins 2 to 9 were obtained in the same manner as in the production example of crystalline polyester resin 1, except that the formulation was changed as shown in Table 1. The compositions and physical properties of crystalline polyester resins 2 to 9 are shown in Table 1.
[0120] [Table 1]
[0121] <Production Example of Amorphous Polyester Resin 1> Terephthalic acid 30.0 parts Isophthalic acid 10.0 parts Sebacic acid 15.0 parts Dodecenyl succinic acid 20.0 parts Trimellitic acid 6.9 parts Bisphenol A ethylene oxide (2 moles) adduct 70.0 parts Bisphenol A propylene oxide (2 moles) adduct 90.0 parts Dibutyltin oxide 0.1 parts The above materials were placed in a heated and dried two-neck flask, and nitrogen gas was introduced into the container to maintain an inert atmosphere and raise the temperature while stirring. After that, a condensation polymerization reaction was carried out at 150°C to 230°C for about 13 hours, and then the pressure was gradually reduced at 210°C to 250°C to obtain amorphous polyester resin 1. The amorphous polyester resin 1 had a number average molecular weight (Mn) of 19,400, a weight average molecular weight (Mw) of 85,000, and a glass transition temperature (Tg) of 58°C.
[0122] <Production Example of Amorphous Polyester Resin 2> Terephthalic acid 28.0 parts Isophthalic acid 10.0 parts Sebacic acid 17.0 parts Dodecenyl succinic acid 20.0 parts Trimellitic acid 6.9 parts Bisphenol A ethylene oxide (2 moles) adduct 68.0 parts Bisphenol A propylene oxide (2 moles) adduct 92.0 parts Dibutyltin oxide 0.1 parts The above materials were placed in a heated and dried two-neck flask, and nitrogen gas was introduced into the container to maintain an inert atmosphere and raise the temperature while stirring. After that, a condensation polymerization reaction was carried out at 150°C to 230°C for about 13 hours, and then the pressure was gradually reduced at 210°C to 250°C to obtain amorphous polyester resin 2. The amorphous polyester resin 2 had a number average molecular weight (Mn) of 14,200, a weight average molecular weight (Mw) of 69,000, and a glass transition temperature (Tg) of 56°C.
[0123] <Production Example of Amorphous Polyester Resin 3> Terephthalic acid 48.0 parts Dodecenyl succinic acid 17.0 parts Trimellitic acid 10.2 parts Bisphenol A ethylene oxide (2 moles) adduct 80.0 parts Bisphenol A propylene oxide (2 moles) adduct 74.0 parts Dibutyltin oxide 0.1 parts The above materials were placed in a heated and dried two-neck flask, and nitrogen gas was introduced into the vessel to maintain an inert atmosphere and raise the temperature while stirring. After that, a condensation polymerization reaction was carried out at 150°C to 230°C for about 13 hours, and then the pressure was gradually reduced at 210°C to 250°C to obtain amorphous polyester resin 3. The amorphous polyester resin 3 had a number average molecular weight (Mn) of 21,200, a weight average molecular weight (Mw) of 98,000, and a glass transition temperature (Tg) of 58°C.
[0124] <Production Example of Amorphous Polyester Resin 4> Terephthalic acid 40.0 parts Dodecenyl succinic acid 10.5 parts Trimellitic acid 16.5 parts Bisphenol A ethylene oxide (2 moles) adduct 70.0 parts Bisphenol A propylene oxide (2 moles) adduct 70.0 parts Dibutyltin oxide 0.1 parts The above materials were placed in a heated and dried two-neck flask, and nitrogen gas was introduced into the vessel to maintain an inert atmosphere and raise the temperature while stirring. After that, a condensation polymerization reaction was carried out at 150°C to 230°C for about 13 hours, and then the pressure was gradually reduced at 210°C to 250°C to obtain amorphous polyester resin 4. The amorphous polyester resin 4 had a number average molecular weight (Mn) of 33,300, a weight average molecular weight (Mw) of 134,000, and a glass transition temperature (Tg) of 61°C.
[0125] <Production Example of Amorphous Polyester Resin 5> Terephthalic acid 40.0 parts Dodecenyl succinic acid 11.5 parts Trimellitic acid 14.4 parts Bisphenol A ethylene oxide (2 moles) adduct 70.0 parts Bisphenol A propylene oxide (2 moles) adduct 70.0 parts Dibutyltin oxide 0.1 parts The above materials were placed in a heated and dried two-neck flask, and nitrogen gas was introduced into the vessel to maintain an inert atmosphere and raise the temperature while stirring. After that, a condensation polymerization reaction was carried out at 150°C to 230°C for about 13 hours, and then the pressure was gradually reduced at 210°C to 250°C to obtain amorphous polyester resin 5. The amorphous polyester resin 5 had a number average molecular weight (Mn) of 23,800, a weight average molecular weight (Mw) of 107,000, and a glass transition temperature (Tg) of 59.8°C.
[0126] <Production Example of Crystalline Polyester Dispersion 1> Into a beaker equipped with a stirrer, 100.0 parts of ethyl acetate, 30.0 parts of crystalline polyester resin 1, 0.3 parts of 0.1 mol / L sodium hydroxide, and 0.2 parts of an anionic surfactant (Neogen RK, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were placed, heated to 60.0°C, and stirring was continued until completely dissolved. With further stirring, 90.0 parts of ion-exchanged water was gradually added, phase inversion emulsification was carried out, and the solvent was removed, thereby obtaining a crystalline polyester dispersion 1 (solid content concentration: 20% by mass). The volume average particle size of the resin particles in the crystalline polyester dispersion 1 was 0.17 μm.
[0127] <Production Examples of Crystalline Polyester Dispersions 2 to 9> Crystalline polyester dispersions 2 to 9 were obtained in the same manner as in Production Example of Crystalline Polyester Dispersion 1, except that the crystalline polyester resins used were as shown in Table 2. The formulations and physical properties are shown in Table 2.
[0128] <Production Examples of Amorphous Resin Dispersions 1 to 5> Amorphous resin particle dispersions 1 to 5 were obtained in the same manner as in the production example of crystalline polyester dispersion 1, except that the crystalline polyester resin used was changed to an amorphous polyester resin as shown in Table 2. The formulations and physical properties are shown in Table 2.
[0129] <Production Example of Amorphous Resin Dispersion 6> Styrene 79.0 parts n-Butyl acrylate 19.0 parts β-Carboxyethyl acrylate 2.0 parts 1,6-Hexanediol diacrylate 0.4 parts Dodecanethiol (Wako Pure Chemical Industries, Ltd.) 0.7 parts The above materials were put into a flask, mixed and dissolved to obtain a solution. The obtained solution was dispersed and emulsified in an aqueous medium prepared by dissolving 1.0 part of an anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK) in 250 parts of ion-exchanged water. While slowly stirring and mixing for 10 minutes, 50 parts of ion-exchanged water in which 2 parts of ammonium persulfate were dissolved was further added. Next, the system was thoroughly replaced with nitrogen, and then the system was heated in an oil bath with stirring until the temperature inside the system reached 70° C., and emulsion polymerization was continued for 5 hours to obtain Amorphous Resin Dispersion 6 (solid concentration: 20% by mass). The resin particles in the amorphous resin dispersion 6 had a volume average particle size of 0.19 μm, a glass transition temperature (Tg) of 58° C., and a weight average molecular weight (Mw) of 75,000.
[0130] [Table 2]
[0131] <Production Example of Wax Dispersion 1> Behenyl behenate (melting point 72°C) 50.0 parts 0.3 parts anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK) 150.0 parts ion-exchanged water The above was mixed and heated to 95°C, and dispersed using a homogenizer (IKA Ultra Turrax T50). After that, it was dispersed using a Manton-Gaulin high pressure homogenizer (Gaulin) to prepare wax dispersion 1 (solid concentration: 20% by mass) in which wax particles were dispersed. The volume average particle size of the obtained wax particles was 0.22 μm.
[0132] <Production Example of Wax Dispersion 2> Wax dispersion 2 (solid content: 20% by mass) was obtained in the same manner as in Production Example 1 of Wax Dispersion 1, except that the wax used was a hydrocarbon wax (melting point: 72° C.).
[0133] <Production Example of Colorant Dispersion 1> CI Pigment Yellow 155: 1000 copies Anionic surfactant: 150 parts Ion-exchanged water: 9,000 parts The above was mixed and dissolved, and then dispersed using a high-pressure impact disperser to prepare Colorant Dispersion 1 (solid content concentration: 20% by mass). The volume average particle size of the obtained colorant particles was 0.16 μm.
[0134] <Production example of powder adhesive particle 1> ·Amorphous resin dispersion 1 (solid content 20% by mass) 150.0 parts Crystalline polyester dispersion 1 (solid content 20% by mass) 65.0 parts Wax dispersion 1 (solid content 20% by mass) 20.0 parts Colorant dispersion 1 (solid content 20% by mass) 0.1 parts The above materials were placed in a beaker, and the total parts of water was adjusted to 250 parts, and then the temperature was adjusted to 30.0° C. Then, the materials were mixed by stirring at 5000 rpm for 1 minute using a homogenizer (IKA Ultra Turrax T50). Furthermore, 10.0 parts of a 2.0 mass% aqueous solution of aluminum chloride, which is a polyvalent metal compound, was gradually added as a flocculant. The raw material dispersion was transferred to a polymerization kettle equipped with a stirrer and a thermometer, and heated to 50.0°C with a mantle heater and stirred to promote the growth of flocculant particles. After 60 minutes had elapsed, 200.0 parts of a 5.0 mass % aqueous solution of ethylenediaminetetraacetic acid (EDTA) was added to prepare aggregated particle dispersion 1. Subsequently, the pH of aggregated particle dispersion 1 was adjusted to 8.0 using a 0.1 mol / L aqueous solution of sodium hydroxide, and then aggregated particle dispersion 1 was heated to 80.0° C. and left for 180 minutes to allow the aggregated particles to coalesce. After 180 minutes, the powder adhesive particles were dispersed to obtain powder adhesive particle dispersion 1. After cooling to 40°C or less at a temperature drop rate of 300°C / min, powder adhesive particle dispersion 1 was filtered and washed with ion-exchanged water. When the conductivity of the filtrate became 50 mS or less, the powder adhesive particles that had become cake-like were taken out. Next, the cake-like powder adhesive particles were placed in ion-exchanged water in an amount 20 times the mass of the powder adhesive particles, stirred with a three-one motor, and when the powder adhesive particles were sufficiently loosened, they were filtered again, washed with water, and separated into solid and liquid. The resulting cake-like powder adhesive particles were crushed with a sample mill and dried in an oven at 40°C for 24 hours. The obtained powder was further crushed in a sample mill and then subjected to additional vacuum drying in an oven at 50° C. for 5 hours to obtain powder adhesive particles 1.
[0135] <Production example of powder adhesive 1> 100 parts of powder adhesive particle 1 were treated with 0.5 parts of the following inorganic fine particles A1, 0.3 parts of the following fine particles B1, and silica fine particles having a number average particle size of the primary particles of 12 nm with silicone oil, and the BET specific surface area after treatment was 120 m 20.8 parts of hydrophobic silica fine particles having a molecular weight of 1 / g were added and mixed using an FM mixer (manufactured by Nippon Coke and Engineering Co., Ltd.) to obtain powder adhesive 1. The physical properties of the obtained powder adhesive 1 are shown in Tables 7 and 9.
[0136] <Inorganic fine particles A> Table 3 shows the type and physical properties of the inorganic fine particles A used.
[0137] [Table 3]
[0138] <Fine particles B> The type and physical properties of the fine particles B used are shown in Table 4.
[0139] [Table 4]
[0140] <Production examples of powder adhesives 2-13, 15-32> Powder adhesives 2 to 13 and 15 to 32 were obtained in the same manner as in the production examples of powder adhesive particle 1 and powder adhesive 1, except that the types and amounts of amorphous resin dispersion, crystalline polyester dispersion, wax dispersion, colorant dispersion, and polyvalent metal compound used, and the temperature at which the aggregated particles were mixed were changed as shown in Table 5, and the types and amounts of inorganic fine particles A and fine particles B were changed as shown in Table 6. The physical properties are shown in Tables 7 and 9.
[0141] <Production example of powder adhesive 14> Amorphous polyester resin 1: 30.0 parts Crystalline polyester resin 1: 13.0 parts Behenyl behenate (melting point 72°C): 4.0 parts Aluminum chloride: 0.2 parts The above materials were premixed in an FM mixer (manufactured by Nippon Coke and Engineering Co., Ltd.), and then melt-kneaded using a twin-screw extruder (product name: PCM-30, manufactured by Ikegai Iron Works Co., Ltd.) with the temperature set so that the molten temperature at the discharge outlet was 150°C. The obtained kneaded product was cooled, coarsely pulverized with a hammer mill, and then finely pulverized with a pulverizer (product name: Turbo Mill T250, manufactured by Turbo Kogyo Co., Ltd.) The obtained finely pulverized powder was classified with a multi-division classifier utilizing the Coanda effect to obtain powder adhesive particles 14. Powder adhesive 14 was obtained in the same manner as in the production example of powder adhesive 1, except that the types and amounts of external additives used were as shown in Table 6. The physical properties of powder adhesive 14 are shown in Tables 7 and 9.
[0142] [Table 5] The unit of the concentration of the polyvalent metal compound in the aqueous solution is mass %.
[0143] [Table 6]
[0144] [Table 7]
[0145] <Production Example of Toner Particle 1> ·Amorphous resin dispersion 1 (solid content 20% by mass) 150.0 parts Crystalline polyester dispersion 1 (solid content 20% by mass) 22.0 parts Wax dispersion 1 (solid content 20% by mass) 20.0 parts Colorant dispersion 1 (solid content 20% by mass) 15.0 parts The above materials were placed in a beaker, and the total parts of water was adjusted to 250 parts, and then the temperature was adjusted to 30.0° C. Then, the materials were mixed by stirring at 5000 rpm for 1 minute using a homogenizer (IKA Ultra Turrax T50). Furthermore, 10.0 parts of a 2.0 mass% aqueous solution of aluminum chloride, which is a polyvalent metal compound, was gradually added as a flocculant. The raw material dispersion was transferred to a polymerization kettle equipped with a stirrer and a thermometer, and heated to 50.0°C with a mantle heater and stirred to promote the growth of flocculant particles. After 60 minutes had elapsed, 200.0 parts of a 5.0 mass % aqueous solution of ethylenediaminetetraacetic acid (EDTA) was added to prepare aggregated particle dispersion 1. Subsequently, the pH of aggregated particle dispersion 1 was adjusted to 8.0 using a 0.1 mol / L aqueous solution of sodium hydroxide, and then aggregated particle dispersion 1 was heated to 80.0° C. and left for 180 minutes to allow the aggregated particles to coalesce. After 180 minutes, toner particle dispersion liquid 1 in which powder adhesive particles were dispersed was obtained. After cooling to 40°C or less at a temperature drop rate of 300°C / min, toner particle dispersion liquid 1 was filtered and washed with ion-exchanged water. When the conductivity of the filtrate became 50mS or less, the toner particles in the form of a cake were taken out. Next, the cake-like toner particles were placed in ion-exchanged water in an amount 20 times the mass of the toner particles, stirred with a three-one motor, and when the toner particles were sufficiently loosened, they were filtered again, washed with water, and separated into solid and liquid. The resulting cake-like toner particles were crushed in a sample mill and dried in an oven at 40°C for 24 hours. The resulting powder was then crushed in a sample mill. After that, additional vacuum drying was carried out in an oven at 50° C. for 5 hours to obtain toner particles 1.
[0146] <Toner 1 Manufacturing Example> 100 parts of toner particles 1 are treated with silica fine particles having a primary particle number average particle size of 12 nm with silicone oil, and the BET specific surface area after treatment is 120 m 2 The mixture was mixed using an FM mixer (manufactured by Nippon Coke and Engineering Co., Ltd.) to obtain toner 1. The physical properties of Toner 1 are shown in Tables 8 and 9.
[0147] <Production Examples of Toners 2 to 14> Toners 2 to 14 were obtained in the same manner as in the production example of toner particle 1 and toner 1, except that the types and amounts of the amorphous resin dispersion, crystalline polyester dispersion, wax dispersion, colorant dispersion, and polyvalent metal compound used were changed as shown in Table 8. The physical properties of toners 2 to 14 are shown in Tables 8 and 9.
[0148] [Table 8] The unit of the concentration of the polyvalent metal compound in the aqueous solution is mass %.
[0149] Developer sets were prepared using the obtained powder adhesives and toners in the combinations shown in Table 9. Developer sets 1 to 30 were used as examples, and comparative developer sets 1 to 7 were used as comparative examples.
[0150] [Table 9]
[0151] The obtained developer sets 1 to 30 and comparative developer sets 1 to 7 were subjected to performance evaluation according to the following method. The evaluations were all performed in a normal temperature and humidity (25°C / 50% RH) environment, and the paper used was A4 size GFC-081 (81.0 g / m 2 ) (Canon Marketing Japan) was used. The results are shown in Table 10.
[0152] <Evaluation of Adhesion Strength and High Temperature Offset Resistance> (Preparation of sample images for evaluation) A commercially available Canon laser beam printer LBP712Ci was used to create the sample images for evaluation. The software was modified so that the printer could operate even if all cartridges were not set. The amount of powder adhesive and toner applied (mg / cm2) was also measured. 2 ) can be adjusted arbitrarily. The toner in the cyan cartridge of the LBP712Ci was removed, and 150 g of the toner of each developer set was refilled and set in the cyan station. The toner in the black cartridge was removed, and 150 g of the powder adhesive of each developer set was refilled and set in the black station. Using this printer, as shown in Figure 8, a powder adhesive was applied in an area of 4 cm with an 8 cm margin at the tip of one side of the paper (the adhesive side) at a rate of 0.5 mg / cm. 2 Print with powder On the side opposite to the adhesive (the side to be printed with toner), a margin of 14 cm is left, and toner is applied in an area of 4 cm with a quantity of 0.08 mg / cm. 2 (Image A). Furthermore, as shown in Figure 9, a separate piece of paper was left with a margin of 8 cm at the tip, and powder adhesive was applied to an area of 4 cm at a rate of 0.5 mg / cm. 2 (Image B). The obtained image A was cut to a width of 3 cm to obtain sample A. Similarly, image B was cut to obtain sample B.
[0153] (Evaluation of adhesion temperature of powder adhesives) As shown in Figure 10, Sample A and Sample B were placed facing each other with the powder adhesive surfaces facing inward, and passed through the external fixing unit removed from the LBP712Ci with Sample A facing up, to evaluate the adhesive strength of the powder adhesive and the toner's high-temperature offset resistance. Specifically, multiple sets of Sample A and Sample B were prepared and passed through an external fixing device while changing the set temperature in 2°C increments. In the adhesive strength evaluation method described below, the adhesive strength of the powder adhesive was 1.2 (N / cm 2 The lowest setting temperature of the fixing unit at which the adhesion strength at low temperatures is 100% was evaluated as the adhesion temperature. The lower the adhesion temperature, the better the adhesion strength at low temperatures. The maximum fixing temperature at which the toner's high-temperature offset occurs was evaluated as the high-temperature offset resistance temperature. The higher the high-temperature offset resistance temperature, the better the high-temperature offset resistance. The method for evaluating the high-temperature offset resistance will be described later. The difference between the adhesion temperature and the high-temperature offset resistance temperature is defined as the fixing region, and the larger the fixing region, the greater the fixing margin, indicating an excellent developer set.
[0154] (Adhesive strength evaluation) A Tensilon universal testing machine RTG-1225 (manufactured by A&D Co., Ltd.) was used to evaluate the adhesive strength. A parallel clamping jaw was used as the jig, and the bonded sample was set as shown in Figure 11. The horizontal axis indicates the distance (mm) obtained when the sample image for evaluation was peeled off at a speed of 50 mm / min, and the vertical axis indicates the stress (N / cm 2The stress per 1 cm width is calculated by multiplying the maximum value in the graph by 1 / 3 and expressing it as the adhesive strength (N / cm 2 The higher this value, the better the adhesive strength. Adhesive strength that can be judged to be sufficient is 1.2 (N / cm 2 ) is used as the evaluation criteria.
[0155] (Evaluation of high temperature offset resistance) When sample A and sample B are placed facing each other with the powder adhesive surfaces facing inward and passed through a fixing unit with sample A on the top, if high-temperature offset occurs, the high-temperature offset toner will be printed downstream of the toner printing area on the paper. The density of the toner resulting from high-temperature offset printed on the paper was measured to evaluate high-temperature offset resistance. A reflectometer (Tokyo Denshoku Co., Ltd.'s "REFLECTOMETER MODEL TC-6DS") was used to measure the density. The reflectance Dr (%) of the toner portion resulting from offset on the paper and the reflectance Ds (%) of the white portion of the paper were measured, and the reflectance was calculated using the following formula. Toner density due to high temperature offset (%) = Dr (%) - Ds (%) The maximum fixing unit set temperature at which this value does not exceed 0.4 is defined as the high-temperature offset resistance temperature.
[0156] <Wrinkle evaluation> The evaluation of wrinkles on the paper at the adhesive joint was carried out at the high-temperature offset resistance temperature at which wrinkles tend to occur in the evaluation of adhesive strength and high-temperature offset resistance. The number of wrinkles that occurred on both pieces of paper sandwiching the adhesive joint was counted. The fewer the number of wrinkles, the better.
[0157] <Curl evaluation> The sample was passed through the fixing unit and left for 24 hours at a temperature of 23°C and a relative humidity of 50%, after which the amount of curl of the sample was measured. The height was measured with a ruler and evaluated as the curl height. The samples for which curl was evaluated were subjected to the evaluation of adhesive strength and high-temperature offset resistance at a high-temperature offset resistance temperature at which curling is likely to occur. The smaller the curl height, the better.
[0158] <Evaluation of seepage> The paper used to evaluate the bleeding was A4 size CS-064 (64.0 g / m 2 ) (Canon Marketing Japan) was used. Samples A and B were prepared using CS-064 in the same manner as in the evaluation of adhesion and high-temperature offset resistance. Next, as a condition under which bleeding is likely to occur, one sample was prepared by passing it through a fixing unit at the high-temperature offset resistance temperature used in the evaluation of adhesion and high-temperature offset resistance. A blank A4-sized sheet of CS-064 was cut to a width of 3 cm to prepare sample C. Sample C was placed on the side of sample A that had been passed through the fixing unit, and 500 sheets of CS-064 paper were then placed on top of that, and left in an environment of 40°C / 30% RH for five days. After that, the adhesive strength between the side of sample A that had been passed through the fixing unit and sample C was measured using the same method as for evaluating adhesive strength above. This is a measurement of adhesive strength due to the seeping-out powder adhesive, so the smaller the number, the better.
[0159] [Table 10] [Explanation of symbols]
[0160] 1...image forming apparatus, 1e...image forming means (image forming unit), 1m...main transport path, 2...scanner unit, 3...transfer unit, 3a...transfer belt, 3b...secondary transfer inner roller, 3c...tension roller, 4...primary transfer roller, 5...transfer means (secondary transfer roller), 5n...transfer nip, 6...fixing means (first fixing device), 6a...heating roller, 6b...pressure roller, 6n...fixing nip, 7n...second process unit (process cartridge), 7y, 7m, 7c...first process unit (process cartridge), 8...sheet cassette, 8a...transport roller, 9...cartridge support section, 10...apparatus main body, 12...discharge port (first discharge port), 13...guide member (first discharge tray), 13...a tray switching guide, 15...intermediate path, 19...first housing, 20...openable tray, 30...sheet processing device (post-processing unit), 31...folding means (folder), 31a...first folding roller, 31b...second folding roller, 31c...first guide roller, 31d...second guide roller, 31e...pulling section, 31f...guide wall, 31g...wall, 31h...end section, 32...adhesive means (second fixing device), 33...switching guide, 33a...switching guide shaft section, 33b...switching guide tip, 34...discharge unit, 34a...first discharge roller, 34b...intermediate roller, 34c...second discharge roller, 35...second discharge tray, 36, 37...connector, 39...second housing, 51...adhesive postcard, 52...medicine bag, 51a...periphery of outer periphery, 51b, 52b...central fold, 52a...U-shaped area, 101...photosensitive drum, 102...charging roller, 103...cleaning member, 104n, 104y, 104m, 104c...powder container, 105...developing roller, 106...developer supply roller, 107...developing blade, 108...agitating member, 109...developing chamber, P...sheet, R1...first path, R2...second path, Tn...powder adhesive, Ty, Tm, Tc...printing toner, CC...photoconductor unit, DT...developing unit, q...leading edge of sheet P, r...middle part, L...total length of sheet P, M...spacing, N...depth of retraction part
Claims
1. 1. An electrophotographic developer set including a toner and a powder adhesive, The powder adhesive contains a crystalline polyester resin and a thermoplastic resin other than the crystalline polyester resin, The content of the crystalline polyester resin in the powder adhesive is 21% by mass or more, The melting point of the crystalline polyester resin is 55° C. or more and 100° C. or less, the crystalline polyester resin contained in the powder adhesive is a condensation polymer of an aliphatic diol having 2 to 12 carbon atoms and an aliphatic dicarboxylic acid having 2 to 12 carbon atoms; the thermoplastic resin contained in the powder adhesive contains an amorphous polyester resin as a main component, The powder adhesive contains a polyvalent metal compound, the polyvalent metal compound is at least one selected from the group consisting of an aluminum compound, an iron compound, and a magnesium compound; In viscoelastic measurements, The storage modulus of the toner at 100° C. is Gt′(100), When the storage modulus of the powder adhesive at 100° C. is Gb′(100), Gb'(100) is 1.0×10 5 Pa or less, Gt'(100) / Gb'(100) is 1.2 or more, The electrophotographic developer set is characterized in that the maximum value of the ratio tan δ of the loss modulus G'' of the powder adhesive to the storage modulus G' of the powder adhesive in the range of 55°C or higher and 100°C or lower is 0.7 or higher and lower than 3.
0.
2. 2. The electrophotographic developer set according to claim 1, wherein the Gt'(100) / Gb'(100) is from 2.0 to 30.
0.
3. In the viscoelasticity measurement, The storage modulus Gb' of the powder adhesive is 1.0×10 4 The temperature at which the temperature becomes Pa is Tb, The storage elastic modulus Gt′ of the toner is 1.0×10 4 When the temperature at which the pressure becomes Pa is Tt, 3. The electrophotographic developer set according to claim 1, wherein Tt-Tb is 10° C. or more.
4. In the viscoelasticity measurement of the powder adhesive, 4. The electrophotographic developer set according to claim 1, wherein a maximum value of a ratio (tan δ) of a loss modulus G″ of the powder adhesive to a storage modulus G′ of the powder adhesive in a temperature range of 55° C. or higher and 100° C. or lower is 0.7 or higher and 2.0 or lower.
5. 5. The electrophotographic developer set according to claim 1, wherein the powder adhesive has an average circularity of 0.940 or more.
6. The powder adhesive has inorganic fine particles A on its surface, The inorganic fine particles A are silica fine particles, 6. The electrophotographic developer set according to claim 1, wherein the inorganic fine particles A have a number average particle size of primary particles of 30 nm or more and 200 nm or less.
7. The powder adhesive has fine particles B on its surface, The volume resistivity of the fine particles B at 25° C. is 5.0×10 Ωm to 1.0×10 8 7. The electrophotographic developer set according to claim 1, wherein the viscosity is Ωm.
8. The toner contains a crystalline polyester resin, 8. The electrophotographic developer set according to claim 1, wherein the content of the crystalline polyester resin in the toner is less than the content of the crystalline polyester resin in the powder adhesive.
9. the powder adhesive contains a colorant; 9. The electrophotographic developer set according to claim 1, wherein the content of the colorant in the powder adhesive is more than 0.00% by mass and not more than 1.00% by mass.
10. A method for producing an adhesive product in which at least one paper is bonded via an adhesive portion, using the electrophotographic developer set according to any one of claims 1 to 9, comprising the steps of: In the adhesive article, a surface of the paper on which the adhesive portion exists is designated as surface A, and a surface other than surface A is designated as surface B. In the adhesive article, at least one of surface B has an image portion formed by the toner, The method for producing the adhesive product includes the steps of: a step of forming an image portion by developing the image portion with the toner on at least one of the surfaces of the paper that will become the surface B and fixing the image portion by heating; and A bonding portion forming step of developing the bonding portion with the powder adhesive on at least one of the surfaces of the paper that will become the surface A and fixing the bonding portion by heating. in any order, Further, the method for producing the bonded article further comprises the steps of: The manufacturing method includes a bonding step of stacking the papers so as to sandwich the formed adhesive portion, heating the papers, and melting the adhesive portion to bond the papers together, thereby obtaining the bonded product.
Citation Information
Patent Citations
Image structure, recording medium, image forming apparatus, and post-processing device
JP2006078545A
Image forming method
JP2006171607A
Transparent toner and method for manufacturing the same, toner set, and image forming method
JP2013130794A
Toner set, developer, and image forming apparatus
JP2014139618A
Toner set
JP2014153661A